Microbiota-derived Indole-3-propionic acid improves FFA-induced liver injury in an in vitro model of nonalcoholic fatty liver disease by activating PINK1/parkin-mediated mitophagy - Qilin Liu; Dahai Wu; Linhua Teng; Gengyang Lin; Huali Huang; Zhihai Liang (Toxicology in Vitro, 2026)

Particle migration and drainage behavior of sand-amended soft clay under staged vacuum preloading: Experiments and LBM–DEM modeling - Xudong Zhang; Weihuang Lin; Yajun Wu; Tianwen Huang; Teng Man; Gen Kondo (Computers and Geotechnics, 2026)

MEK inhibitor cobimetinib increases calreticulin and induces immune modulation in TNBC - Ling-Ming Tseng; Ka-Yi Lau; Ji-Lin Chen; Pei-Yi Chu; Chun-Teng Huang; Wan-Lun Wang; Yuan-Ya Chang; Jiun-I Lai; Chi-Cheng Huang; Ming-Shen Dai; Chun-Yu Liu (Journal of Molecular Medicine, 2026)
Immunogenic cell death (ICD) can activate immune cells and potentiate the response to immunotherapy. The mitogen-activated protein kinase (MAPK) signaling pathway regulates the immune response and mediates T-cell receptor signaling. Activation of the MAPK signaling pathway decreases the levels of tumor-infiltrating lymphocytes in triple-negative breast cancer (TNBC) and is associated with worse survival. Here, we investigated the potential of the MEK inhibitor cobimetinib as an ICD inducer in TNBC. We demonstrated that cobimetinib elicited hallmarks of ICD, including elevated levels of damage-associated molecular patterns. Ectopic ERK expression attenuated cobimetinib-induced CRT. Cobimetinib also evoked caspase-8 activation with increased Bax and Bak expression, while caspase inhibitor suppressed cobimetinib-induced CRT expression and apoptosis. In immunocompetent (BALB/c) mice bearing 4T1 tumors, cobimetinib exhibited stronger tumor growth inhibition than in immunodeficient (nude) mice, suggesting an immune-dependent antitumor effect. Furthermore, cobimetinib treatment increased the proportions of naïve CD8 + T cells and effector CD4 + T cells and decreases the proportion of myeloid-derived suppressor cells in immunocompetent mice bearing 4T1 tumors. Notably, we observed differential immunomodulatory effects of cobimetinib in tumor-bearing mice compared to non–tumor-bearing immunocompetent mice. Our findings indicate that MEK inhibition is associated with ICD-related molecular alterations, and that cobimetinib may contribute to immune modulation in TNBC.

Combined targeting poly (ADP-ribose) polymerase and receptor tyrosine kinase inhibits ovarian clear cell carcinoma progression through disrupted ribosome biogenesis - Chiao-Yun Lin; An-Shine Chao; Angel Chao; Ren-Chin Wu; Alice L. Yu; Chiung-Hui Fu; Yu-Chuan Teng; Ruby Yun-Ju Huang; Chyong-Huey Lai (Journal of Molecular Medicine, 2026)

Novel biallelic LSS variants in autosomal recessive hypotrichosis simplex: insights from a multi-omics approach - Xiaxia Liu; Kai Liu; Yuda Wei; Yongzhen Qi; Yangyang Luo; Tingli Chen; Xiaohua Ye; Junxu Lu; Yunjia Li; Liangqian Jiang; Juan Teng; Xingzhu Geng; et al. (Human Genetics, 2026)

Quorum sensing in meat spoilage: From ecological selection to community-level amplification - Guangfu Zhang; Yuhong Lin; Jinpeng Wang; Yuemei Zhang; Wendi Teng; Shuai Zhuang; Ying Wang; Jinxuan Cao (Trends in Food Science & Technology, 2026)

Ecological connectivity of phytoplankton community in the Xincun Bay lagoon, Hainan Island - Jian Zou; Yayuan Xiao; Lin Lin; Peng Wu; Teng Wang; Yu Liu; Shannan Xu; Yong Liu (Journal of Marine Systems, 2026)

Enhancement by Ce addition to La-Zr-mixed oxide supported Ni catalysts on the mid-temperature steam reforming of methane - Li-Chun Lin; Teng-Li Yu; Cheng-Yao Hung; Guan-Yu Chen; Yi-Ning Chao; Shawn D. Lin (Fuel, 2026)

Chronic paternal exposure to low-dose OBS reprograms progeny's intestinal cholesterol metabolism and increases IBD susceptibility - Wang Yang; Yongsheng Teng; Zeyu Yang; Xiaomei Song; Le He; Yan Liu; Wei Tan; Huihui An; Ping Shi; Chaoqun Hu; Lin Ao; Hong Guo (Environmental Pollution, 2026)

Genomic and biosynthetic landscape of high-temperature Daqu microbiome - Mingyue Cheng; Xing Qin; Ying Han; Fanggen Tan; Menglin She; Xue Zhu; Lin Yuan; Mengjing Teng; Xiyang Ou; Sha Luo; Ping Xiang; Liangqiang Chen; et al. (Bioresource Technology, 2026)

Trace metals in root-stem-leaf of mangrove communities: bioconcentration, migration and biochemical influencing mechanisms in Circum-Xinying-Bay, Hainan, China - Lin Du; Junhao Yang; Chengqian He; Jingyi Cui; Zun Teng; Quan Chen (Marine Pollution Bulletin, 2026)

Lactiplantibacillus plantarum LP15-1 alleviates deoxynivalenol-induced intestinal injury in mice by inhibiting ferroptosis and modulating the gut microbiota - Kunru Teng; Jiefeng Li; Beibei He; Dan Song; Tao Duan; Kuanbo Liu; Lin Qiao; Aike Li; Weiwei Wang; Shijie Fan (Toxicon, 2026)

Physics-environment augmented Attention-LSTM approach for mooring tension prediction - Jin Hu; Dongsheng Qiao; Pengfei Liu; Guoguang Sun; Ziming Wang; Guoqiang Tang; Yunfei Teng; Lin Lu; Jinping Ou (Ocean Engineering, 2026)

Photoexcited directional charge transfer channels on iron-doped bismuth oxybromide for efficient peroxymonosulfate activation in water treatment - Kai Teng; Yi Tao; Mengwei Wu; Chang Liu; YeFei Su; Jiangjun Lin; Qing Qu; Lei Li (Journal of Environmental Chemical Engineering, 2026)

Reprogramming oily water separation with Janus membranes: From asymmetric fabrication to engineering perspectives - Mingyi Ying; Bisheng Li; Jiaheng Teng; Xiang Cai; Cheng Chen; Leihong Zhao; Hongjun Lin (Journal of Environmental Chemical Engineering, 2026)

Divergent contributions of acidic and neutralization potential to precipitation acidity across Islet, Urban and Forest sites, northern Taiwan - Chung-Te Chang; Ci-Jian Yang; Chiu-Hsien Wang; Jr-Chuan Huang; Neng-Huei Lin; Teng-Chiu Lin (Environmental Pollution, 2026)

An objective detection method for tinnitus using memristors - Hui Ma; Xiaoyan Ma; Yingying Xuan; Zelin Cao; Lin Li; Kaikai Gao; Mengna Wang; Ruifeng Qiao; Qin Hu; Wentao Yan; Kun Wang; Haoyuan Wang; et al. (Chemical Engineering Journal, 2026)

Sludge-derived biochar-activated peroxymonosulfate as a waste-to-resource pretreatment for sustainable membrane fouling control: Adsorption-oxidation interplay and thermodynamic insights - Mingjing Xie; Biyan Wang; Jiaqi Liu; Xiao Xu; Hanmin Zhang; Meijia Zhang; Xiang Cai; Leihong Zhao; Bisheng Li; Liguo Shen; Jiaheng Teng; Hongjun Lin (Journal of Cleaner Production, 2026)

Intelligent mining of generation operation rules for cascade hydropower reservoirs driven by large language models and knowledge graphs - Zhong-kai Feng; Teng Lin; Wen-jing Niu; Yang Xiao; Tao Yang; Hongwu Tang (Journal of Hydrology, 2026)

Microplastic-derived dissolved organic matter is associated with increased N2O emissions and altered denitrification-related microbial signatures in constructed wetlands - Yong Lin; Dianpeng Li; Mengshuo Liu; Teng Wen; Xuebin Lu; Jun Chen; Shuqing An (Journal of Hazardous Materials, 2026)

Recent progress on hydrogen production via catalytic Auto-thermal methane Reforming: A focus on catalysts and operational parameters - Jun Wan; Peng Liu; Feiyi Zhou; Huajie Lyu; Teng Hu; Keyu Cheng; Yihong Song; Jiabiao Zou; Xiao Zhang; Saisai Lin; Chenghang Zheng; Xiang Gao (Fuel, 2026)

Regional surveillance of non-A-F Salmonella enterica reveals diverse risk profiles, with global genomic insights from Salmonella Worthington - Lei Fang; Guankai Lin; Yuezhuo Wang; Shiqi Lei; Haiyan Li; Xuewei Liu; Chaoyi Wang; Yi Li; Chen Zhang; Guozhi Zhang; Lin Teng; Leyi Zhang (Food Research International, 2026)

Assisted natural regeneration promotes soil carbon stabilization through fungal residue pathways in subtropical forests - Xiangbiao Chen; Zhijie Yang; Teng-chiu Lin; Robin L. Chazdon; Xiaofei Liu; Decheng Xiong; Chao Xu; Shidong Chen; Chengfang Lin; Miaohua Jiang; Yusheng Yang (Forest Ecology and Management, 2026)

Selective reduction of hazardous volatiles from baijiu using spent grain-derived activated carbon: Flavor preservation and DFT-elucidated adsorption mechanisms - Ziyang Wu; Yunran Shen; Yahan Yan; Yaqi Teng; Jie Lin; Huan Cheng; Hehe Li; Jinyuan Sun; Xingqian Ye; Mingquan Huang; Baoguo Sun (Food Chemistry, 2026)

Green synthesis of N-doped hierarchical porous biochar from Artemisia leaf for enhanced peroxydisulfate activation: Synergistic roles of edge nitrogen and carbonyl group - Lin Ge; Zhan Chen; Yuan Pan; Xiansheng Zhang; Teng Li; Xinyi Huang; Binbin Shao; Sheng Liu; Yunze Wang; Yu Zhang; Zhifeng Liu (Environmental Research, 2026)

Physics-informed multi-objective placement of indoor multi-modal sensor nodes using a two-dimensional LBM-based simulation framework - Teng Zhang; Qingyao Qiao; Wenye Lin; Wenji Song; Eric Schuldenfrei; Akilu Yunusa-Kaltungo; Hongshan Guo; Ziping Feng (Building and Environment, 2026)

Assessing the combined impacts of wildfire and climate change on blue and green water resources in the Weihe River Basin - Teng Yu; Xia Li; Lin Qi; Yunlong Liu; Yuchao Wang; Meixin Shuang (Environment, Development and Sustainability, 2026)

Disproportionality analysis of adverse events associated with tyrosine kinase inhibitors in gastrointestinal stromal tumors in the FDA adverse event reporting system - Yibin Teng; Henan Qin; Ying Lin; Aman Wang; Jiwei Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Retraction notice to “Boronic acid-modified bacterial cellulose microspheres as packing materials for enveloped virus removal” [Sci. Total Environ. 859 (2023) 160341] - Zhiyang Lin; Linhan Li; Kaige Song; Bin Yang; Guoqing Zhou; Gengrong Zhang; Jiang Teng; Erlong Wang; Xiaoqiang Liu; Fei Ling; Gaoxue Wang; Tianqiang Liu (Science of The Total Environment, 2026)

Self-cleaning van der Waals lamination for two-dimensional electronics - Chang Liu; Shuimei Ding; Xudong Wang; Guichen Teng; Jinhua Zeng; Ying Zhang; Qianru Zhao; Huiting Wang; Binmin Wu; Shuaiqin Wu; Yan Chen; Tie Lin; et al. (Science Bulletin, 2026)

VMD-SSTM: A sea surface temperature forecast model based on multi-scale information in the Western Indian Ocean - Shutong Liu; Tengfei Xu; Lin Liu; Fei Teng; Peng Ren; Yonggang Wang (Ocean Modelling, 2026)

Pressure gradient hinders particle migration: An LBM-DEM study of clogging in irregular-shaped porous media - Xudong Zhang; Weihuang Lin; Teng Man; Herbert E. Huppert (Computers and Geotechnics, 2026)

Angstrom confined ion transport in graphene oxide membranes enables highly reversible zinc anodes - Lin Huang; Yihao Xu; Teng Deng; Shu Liu; Liping Chen; Yonghong Fu; Lei Dong; Juan Wang; Keyu Xie (Chemical Engineering Journal, 2026)

AlgaePath 2.0: An updated database for revealing algal coding and non-coding gene interactions in metabolic pathways - Kuan-Chieh Tseng; Wen-Lin Wang; Yen-Lin Shen; Hung-Teng Wang; Ching-Ya Yuan; Chien-Wen Yang; Ching-Nen Nathan Chen; Wen-Chi Chang (Algal Research, 2026)

ERBB2 as a Prognostic Biomarker in Prostate Cancer: Integration of Single-Cell Transcriptomics, Deep Learning, and Immunohistochemical Validation - Chen Wang; Li-Jing Zhu; Wei-Bo Mao; Ting Chen; Teng-Fei Gu; Sheng-Ping Hu; Yong-Tao Pan; Guo-Lin Yan; Yun-Peng Dong; Jie Li (Biochemical Genetics, 2026)

FAL1 facilitates cisplatin resistance of lung adenocarcinoma via BMI1/BIM-mediated apoptosis–autophagy interaction - Teng Ma; Yang Xia; Yijiang Chen; Han Lin; Chunfeng Pan (Molecular and Cellular Biochemistry, 2026)

Habitat explains intraspecific leaf morphological and physiological variation in the facultative epiphyte Nephrolepis cordifolia - Rui-Hong Hsu; J. Aaron Hogan; Chiao-Ping Wang; Teng-Chiu Lin (Journal of Plant Research, 2026)
Epiphytic and terrestrial habitats differ markedly in water, nutrient, and light availability and variability, yet few facultative epiphytes successfully grow in both habitats. As a facultative epiphyte, Nephrolepis cordifolia provides a valuable opportunity to investigate how individuals of the same species adjust morphological and physiological traits along contrasting microhabitats. We measured frond structure, physiology, and tissue nutrient concentrations for 20 epiphytic and 20 terrestrial N. cordifolia individuals to evaluate intraspecific variation in resource-use strategies by growth habitat. Our findings show that not all Leaf Economic Spectrum traits covary in this species. Structurally, while specific leaf area, leaf dry matter content, and stomatal morphology were conserved across habitats, epiphytic individuals exhibited greater leaf thickness, a trait consistent with conservative leaf economics strategies. Functionally, epiphytes exhibited more enriched δ 13 C, indicating higher intrinsic water-use efficiency and tighter stomatal regulation. Terrestrial individuals displayed significantly higher maximum quantum yield of PSII ( F v / F m ) and greater mass-based chlorophyll concentrations, reflecting higher potential photosynthetic capacity. In terms of leaf tissue chemistry, terrestrial individuals had higher nitrogen and magnesium concentrations, while epiphytes showed higher leaf carbon content and significantly elevated C/N ratios. These findings highlight the physiological plasticity of N. cordifolia , which enables adjustment to contrasting microhabitats through adjustments in water-use efficiency, photosynthetic capacity, and leaf chemistry. Our results support the idea that epiphytic plants generally exhibit a more conservative physiological profile, with reduced F v / F m and enriched δ 13 C, showing how they may function under chronically constrained physiological margins. This vulnerability underscores the potential risks epiphytes face under intensifying drought and irradiance associated with climate change, raising important questions about the resilience of facultative epiphytes in increasingly variable environments.

Deep seismic sounding methods for imaging the fine structure of the Earth’s crust - Yurui Guan; Tao Xu; Zhiming Bai; Jiyan Lin; Dengda Zhu; Jiwen Teng (Science China Earth Sciences, 2026)

Management regimes underpin soil carbon accrual following forest conversion to tea plantations across China - Lin Chen; Li Ruan; Yu Duan; Biao Feng; Yixuan Bai; Scott X. Chang; Teng Yang; Yowhan Son; Yuwei Yuan; Shangwen Fu; Chuan Yue; Zhongyi Li; et al. (Science Bulletin, 2026)

Nine previously undescribed immunosuppressive ent-labdane diterpenoids from the roots of Eurysolen gracilis - Lin-Lin Teng; Yan-Chun Liu; Chao-Jiang Xiao; Shu-Xi Jing; De-Sen Li; Ran Xu; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Numerical study on the influence of mangrove density and belt width on wave attenuation characteristics under regular waves - Hongfei Mao; Junxian Teng; Jinbo Lin; Shuidi Yang; Guanglin Wu; Wei Wang; Ya Men (Ocean Engineering, 2026)

Microbial-derived metabolites coordinate growth regulation and stress tolerance in Phalaenopsis orchids - Nur Izzatul Maulidah; I-Hung Lin; Yun-Teng Yen; Ting-Yu Liou; Huey-wen Chuang (Journal of Plant Physiology, 2026)

Microfluidic-based magnetic microspheres for targeted delivery of curcumin nanoparticles in gastroesophageal reflux disease therapy - Haoyao Jiang; Zhonglin Fang; Han Lin; Di Xu; Wanqian Xu; Mengqi Han; Luoran Shang; Ye Zhao; Teng Ma; Di Ge (Chemical Engineering Journal, 2026)

Synergistic atomic-level anchoring and pore engineering of cobalt-nitrogen-carbon for anti-fouling and robust capacitive deionization - Huakun Pan; Haodong Zhang; Xinxi Teng; Yang Fan; Yaming Wang; Lin Li; Guisong Zhang; Meiling Liu; Haiou Song; Aimin Li; Shupeng Zhang (Chemical Engineering Journal, 2026)

Prediction of the long-term evolution of sand waves with a reduced order model—the complex Stuart−Landau equation - Lin Lu; Shilin Wang; Guoqiang Tang; Dongsheng Qiao; Yunfei Teng (Coastal Engineering, 2026)

Osteopontin as an emerging multifunctional food ingredient: recent advancements, production, applications, and challenges - Shiyu Lin; Xiuxiu Teng; Xinjie Shang; Shu Li; Jingjing Xu; Yao Tang; Rui Yang (Critical Reviews in Food Science and Nutrition, 2026)

Role of cholecystokinin (CCK) in reproductive regulation of female mandarin fish (Siniperca chuatsi) - Shuang Liu; Chongwei Wang; Yuting Wang; Chaowei Li; Jinmeng Teng; Suhan Peng; Jiaqi Lin; Jin Zhang; Haoran Lin; Linqiang Han; Ju Hu; Shuisheng Li; et al. (Aquaculture, 2026)

Tandem synergy of hydroxyl radicals and nonradical ferryl for efficient photo-self-Fenton mineralization of refractory pollutants - Ailing Zhang; Meili Liu; Weiqin Wei; Wenwen Jing; Jiayan Teng; Yuanshen Qin; Lin Jing; Yongfa Zhu; Hongxing Dai; Jiguang Deng; Zhen Wei (Water Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Cellulose nanocrystal-based antimicrobial porous foam loaded with cinnamaldehyde for enhanced chilled meat preservation - Jin-ling Wu; Ai-ling Zhong; Rui Zhang; Hai-yan Huang; Teng-gen Hu; Zhen-lin Xu; Hong Wang; Peng Wen (Food Packaging and Shelf Life, 2026)

Dual effects of montmorillonite on CO2 hydrate formation kinetics in saline sand–clay systems: Experimental study and growth modeling - Xiran Lin; Ying Teng; Ying Liu; Mingkun Bai; Yiqi Chen; Pengfei Wang; Liangbin Xu; Jinlong Zhu; Songbai Han; Huiru Sun; Senyou An; Jianbo Zhu (Chemical Engineering Journal, 2026)

Amorphous/crystalline heterophase induced S2− migration and oxidation for enhanced oxygen evolution reaction - Yue Huang; Jiejie Li; Yu Liu; Ying-Jie Ma; Lin Zhu; Fu-Rui Teng; Ziqi Tian; Ai-Dong Li (Chemical Engineering Journal, 2026)

Integrating adsorptive filtration and visible-light peroxymonosulfate activation in a Fe3O4@ZIF-67@polydopamine/PTFE membrane for one-pass treating copper–tetracycline mixed wastewater - Zengjian Zhao; Tao Jian; Wenzhe Yu; Jiaheng Teng; Leihong Zhao; Qian Lei; Hongjun Lin (Chemical Engineering Journal, 2026)

Dang-Gui-Bu-Xue-Tang triggers GM-CSF and IL-4 secretion corporated with increased amount of Immunoglobulins - Sheng-Teng Huang; Jia-Hau Yen; Yu-Chun Lin; Ming-Ching Kao; Chia-Ju Chuang; Shu-Tuan Chiang; Te-Mao Li (Advances in Traditional Medicine, 2026)

Harnessing dual-stable conformers in o-carborane-based multi-resonance emitters for achieving single-emitter white OLEDs - Zezhu Xiao; Chen-Yu Lin; Jianxing Chen; Songqian Ni; Xingtian Wang; Ming-Yu Teng; Weiguo Zhu; Pi-Tai Chou; Xiugang Wu (Chemical Engineering Journal, 2026)

Development of an “Off-On” Fluorescence Sensing System Based on Nitrogen-Doped Carbon Quantum Dot/Fe³⁺ for Sensitive Detection of Cysteine - Lihao Jiang; Wenjie Dong; Yongjian Pan; Jianyuan Lin; Shancai Guo; Teng Wang; Fuhang Xu; Haili Wang; Chunjie Bai; Lihua Teng; Jianghua Chen (Journal of Fluorescence, 2026)

Generation and characterization of the Il11-Cre knock-in mouse - Xuetao Zhou; Zhongliang Xie; Wenjia Liu; Qingye Wang; Huisang Lin; Rongyu Li; Yiming Lang; Jun Chen; Xiao Yang; Yan Teng; Guan Yang (Transgenic Research, 2026)

Wave forces of subsea cables laid on meso-scale rough seabeds - Zhe Gao; Dang Zhao; Yunfei Teng; Yuanyuan Xu; Liang Cheng; Guoqiang Tang; Lin Lu; Dongsheng Qiao (Ocean Engineering, 2026)

Supramolecularly cross-linked aramid-PVDF-aramid sandwich electrolytes with continuous Li+ pathways for ultralong cycle life in solid-state lithium metal batteries - Jianhong Xu; Dehua Li; Xiao Yang; Yingyuan Ma; Xinrui Zheng; Panpan Shen; Di Zhang; Weiyu Teng; Yuting Lin; Yi Hu (Chemical Engineering Journal, 2026)

Schaftoside inhibits neuroinflammation and exerts antidepressant effects through METTL3-mediated m6A modification of circ_0001470 sponging miR-183-5p to regulate MAP3K1 expression - Haohao Wang; Jinxiang Wu; Keren Ma; Ting Su; Qiyan Lin; Hongyan Zhang; Teng Ma; Pan Wang; Dong Liu (Psychopharmacology, 2026)

Oxygen vacancy engineered M0.5Ni0.5Fe2O4 for enhanced chemical looping combustion performance - Xinyu Li; Jianshuai Li; Lina Wang; Lei Liu; Yan Lin; Shenglong Teng; Yiwen Song; Dewang Zeng; Yu Qiu (Chemical Engineering Journal, 2026)

Multi-scale assessment of energy transition and emission patterns in industrial coastal regions - Ying Teng; Mingkun Bai; Xiran Lin; Jiajie Li; Tao Zhang; Shuyang Liu; Senyou An; Liangbin Xu; Pengfei Wang; Songbai Han; Jinlong Zhu; Jianbo Zhu; et al. (Fuel, 2026)

Migration of dissolved organic matters in riparian soils induced by rainfall: distribution between surface and subsurface runoffs - Chang Liu; Lin Li; Yue Zhi; Yinying Zhu; Teng Hu; Qiang He (Environmental Research, 2026)

Bulk metagenomics and machine learning unravels nitrogen metabolism patterns in extreme-temperature marine environments - Zheng Guo; Yong-Guang Li; Xiao-Lin Liu; Zhao-Jie Teng; Qi-Long Qin; Qian-Qian Cha; Zhi-Bin Wang; Shou-Qing Ni (Bioresource Technology, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

A novel single-cell communication framework combining multi-omics reveals neuro-viral pathogenesis in fish - Yi-Fan Liu; Teng-Fei He; Zhi-Wen Zhao; Bao-Sheng Wu; Ying Liang; Lin-Miao Li; Jin-Ping Chen; Ye-Pin Yu (Marine Life Science & Technology, 2026)

Open the door to the new world of singlet oxygen in the peracetic acid system: Generation and identification - Rui Liu; Wen Lu; Yuting Liu; Mingzhu Zhou; Bisheng Li; Hongjun Lin; Jiaheng Teng; Liguo Shen; Xiaohong Guan; Leihong Zhao (Water Research, 2026)

Multiscale thermodynamic insights into membrane fouling control by biochar-activated peroxymonosulfate pretreatment: Synergy of oxidation and adsorption - Mingjing Xie; Wenfa Yang; Xiaoni Zhou; Biyan Wang; Jiaqi Liu; Xiao Xu; Liguo Shen; Hanmin Zhang; Meijia Zhang; Wei Yu; Jiaheng Teng; Hongjun Lin; et al. (Water Research, 2026)

Ripened Pu-erh tea modulates the gut microbiome to enhance metabolic homeostasis and redox-inflammatory balance: A systematic review of core health benefits and mechanisms - Ming Zhao; Teng Wang; Lin Zeng; Qiuyue Chen; Dihan Yang; Yiqing Guan; Nianguo Bo; Yong-Quan Xu; Yan Ma (Trends in Food Science & Technology, 2026)

RG7388 inhibits SFTSV replication by suppressing MDM2-mediated p53 degradation and preventing apoptosome disruption - Zixiang Liu; Mengqian Huang; Yuyang Liu; Luna Cui; Xixi Shi; Honghua Chen; Xiaoning Gao; Zining Wang; Qinting Lin; Zhiyun Wang; Yue Teng; Tao Wang (Science Bulletin, 2026)

A dual-band parametric method for angular normalization of land surface thermal radiation for single-angle thermal infrared image - Yuanjian Teng; Huazhong Ren; Songyi Lin; Fengguang Li; Yunzhu Tao; Xue Zhong; Qiming Qin (Remote Sensing of Environment, 2026)

Do biodegradable plastic residues pose lower ecological risks to crops than conventional plastic residues? A meta-analytic comparison - Feng Yuan; Teng Wang; Hongyu Chen; Yongcheng Ding; Jianguo Tao; Yue Xue; Linjie Zhang; Haiyan Lin; Baojie Li; Yifei Qiu; Guanghe Fu; Xinqing Zou (Journal of Hazardous Materials, 2026)

Predicting in-situ CO2 solubility in formation brines using Raman spectroscopy and machine learning: Implications for offshore geological carbon storage - Ying Teng; Yiqi Chen; Xiran Lin; Mingkun Bai; Senyou An; Shuyang Liu; Pengfei Wang; Tao Zhang; Songbai Han; Jinlong Zhu; Jianbo Zhu; Heping Xie (Gas Science and Engineering, 2026)

Unraveling the structure-selectivity nexus: electrode materials for selective phosphorus removal and recovery via capacitive deionization: A systematic review - Sheng Wen; Yu Ma; Yang Fan; Jinxing Lin; Jiaqi Chen; Simiao Li; Huakun Pan; Xinxi Teng; Shupeng Zhang (Chemical Engineering Journal, 2026)

Harnessing pyroptosis to restrain melanoma through aripiprazole - Yu-Teng Chang; I-Hsiang Lin; Jeng-Jer Shieh; Tsuo-Hung Lan; Jia-Ning Syu; Shiau-Shian Huang; Po-Hsun Hou (Apoptosis, 2026)

The glymphatic system in psychiatric disorders: a new perspective - Teng Gao; Zhe Wang; Serik Tabarak; Qingqing Yin; Lin Lu (Science Bulletin, 2025)

Satellite mapping of emperor penguin habitat dispersal under climate extremes - Hong Lin; Xiao Cheng; Jinyang Du; John S. Kimball; Ziyu Yan; Teng Li; Tongwen Li; Yibo Li; Zilong Chen (Remote Sensing of Environment, 2025)

Preparation of activated carbon/liquid paraffin/metakaolin composite geopolymer microspheres using acid leaching and its removal of ReO4−/TcO4− - Kaituo Wang; Qian Li; Teng Lv; Min Yi; Liu He; Xinpeng Wang; Lin Shao (Journal of Water Process Engineering, 2025)

From “single-point benefit” to “chain-level Differentiation”: A study on the supply chain spillover effect of government subsidies - Yuqiang Teng; Boqiang Lin (Journal of Environmental Management, 2025)

Release of microplastics from polyvinyl chloride pipes: Using accelerated aging by ozonation, chlorination and heating to assess the release potential - Yu-Teng Ji; Yi-Chin Cho; Jenyuk Lohwacharin; Yi-Pin Lin (Journal of Environmental Chemical Engineering, 2025)

Thiol-ene click synthesis of a novel alginate-derived adsorbent: Synergistic adsorption and mechanistic investigation of dye and antibiotic - Xinyi Lu; Wei Yu; Chenglin Ji; Longyufan Liu; Jiaheng Teng; Cheng Chen; Hongjun Lin; Guanhua Jin; Leihong Zhao; Saleem Raza; Liguo Shen (Desalination, 2025)

Neutrophil extracellular trap (NET)-targeted nanoparticles alleviate myocardial ischemia–reperfusion injury in mice by inhibiting macrophage–myofibroblast transition - Da Lu; Wei Jiang; Xi Zhang; Jiangshui Liang; Meng Xiong; Changzhi Yan; Anyi Lin; Teng Ma; Feng Zhu; Yongqiang Dong (Chemical Engineering Journal, 2025)

Synergistic enhancement of CO2 hydrate growth by montmorillonite and tryptophan: Insights from piecewise kinetic modeling - Xiran Lin; Ying Teng; Mingkun Bai; Yiqi Chen; Pengfei Wang; Liangbin Xu; Senyou An; Jianbo Zhu; Jinlong Zhu; Songbai Han (Chemical Engineering Journal, 2025)

Hydrodynamic forces on small-diameter pipelines in combined wave-and-current flows - Yunfei Teng; Terry Griffiths; Hongwei An; Scott Draper; Liang Cheng; Henning Mohr; Cheng Zhang; Guoqiang Tang; Lin Lu (Coastal Engineering, 2025)

Identification, characterization, and expression profiling of rice MADS-box transcription factor genes associated with fluroxypyr-meptyl and oxyfluorfen metabolism - Zhi Zhong Zhou; Nian Hua Teng; Jia Lin Liang; Ying Yu Zeng; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetica, 2025)

Functional Analysis of the mstn1 Gene and Its Transcriptional Regulation by Mef2 Factors in Yellowfin Seabream, Acanthopagrus latus (Hottuyn, 1782) - Hong-Xi He; Ke-Cheng Zhu; Bao-Suo Liu; Hua-Yang Guo; Nan Zhang; Lin Xian; Teng-Fei Zhu; Dian-Chang Zhang; Min Yang (Fish Physiology and Biochemistry, 2025)

Levonorgestrel-induced sex reversal in mandarin fish (Siniperca chuatsi): An effective protocol for all-female production and its aquaculture applications - Shiyan Liu; Jinmeng Teng; Suhan Peng; Shuang Liu; Jiaqi Lin; Long Chen; Ju Hu; Haoran Lin; Caiyun Sun; Shuisheng Li; Songlin Chen; Chong Han; et al. (Animal Reproduction Science, 2025)

Potent phenolics with antimigratory and anti-MRSA powers from fungus associated with Saussurea involucrata - Wei-hua Yuan; Meng-ting Teng; Lin Ma; Yan-feng Wan; Kai-yue Lu; Yan-hui Shi; Peng Zhang (Natural Product Research, 2025)

Lignosulfonate provides a sustainable strategy for soil acidification mitigation through dual suppression of nitrification-driven protons and active aluminum - Mao Gao; Yan Yang; Zhuoran Teng; Yuchen Shu; Huijuan Duan; Feixiang Li; Chengliang Sun; Xianyong Lin (Journal of Cleaner Production, 2025)

Advanced membrane technology for per- and polyfluoroalkyl substances removal: Innovations in membrane materials and hybrid systems - Wei Yu; Jiaheng Teng; Xiang Cai; Liguo Shen; Genying Yu; Bisheng Li; Leihong Zhao; Hongjun Lin (Journal of Environmental Management, 2025)

Magnesium-enriched biochar as a multifunctional carrier: unlocking productivity and stability in the algal-bacterial symbiosis system - Xiu Zhang; Xiang Cai; Xin Hu; Chenlu Zong; Hongjun Lin; Liguo Shen; Jiaheng Teng; Bisheng Li; Leihong Zhao; Meijia Zhang (Chemical Engineering Journal, 2025)

Formoterol, a clinically approved drug, inhibits ferroptosis by suppressing lipid peroxidation and attenuates APAP-induced acute liver injury - Lin-Song Teng; Zhen-Dong Ying; Xiao-Han Sun; Hao-Cheng Hou; Shi-Dong Qiu; Peng Liu; Ke-Jing Li; Lei Zhang; Xie-Huang Sheng (Chemico-Biological Interactions, 2025)

Temporal variability of greenhouse gas fluxes in monoculture of tilapia in ponds - Yi–Jung Chen; Han–Yang Yeh; Chien-Wei Tu; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; Ruei-Feng Shiu; Tzu-Ning Teng; Meng–Chou Lee; Fan–Hua Nan (Aquaculture International, 2025)

Molecular dynamics study on coalescence interface evolution of collided dry ice particles - Lin Teng; Wei Lin; Xin Huang; Zhenchao Li; Hongru Li; Pengbo Yin; Shihang Rao (Process Safety and Environmental Protection, 2025)

Associations between element mixtures and biomarkers of pathophysiologic pathways related to autism spectrum disorder - Shiyu Zhang; Hao Zhou; Junfeng (Jim) Zhang; Tianqi Wang; Yanbo Teng; Peng-Chou Tsai; Christine Ladd-Acosta; Yan Lin; Yi Wang (Journal of Trace Elements in Medicine and Biology, 2025)

The impacts of polypropylene microplastics on carbon and nitrogen cycling in coastal wetlands: Field evidence - Feng Yuan; Yue Xue; Zhuoyue Zhang; Jianguo Tao; Yuyang Song; Hongyu Chen; Qihang Liao; Haiyan Lin; Ming Lu; Yongcheng Ding; Teng Wang; Ruize Yang; et al. (Journal of Hazardous Materials, 2025)

Bioreduction-assisted synthesis of Co nanoclusters for selective singlet oxygen generation in ciprofloxacin degradation - Yuning Fan; Wenqian Zhang; Yaping Geng; Jiangjun Lin; Yefei Su; Kai Teng; Jiajie wu; Qing Qu; Lei Li (Journal of Environmental Chemical Engineering, 2025)

Forecasting trajectories of Southern Resident killer whales with stochastic movement models incorporating direction modification - Teng-Wei Lin; Michael Dowd; Ruth Joy (Ecological Modelling, 2025)

Novel CoMo-LDH integration enhanced permeability and self-cleaning of MXene-based membrane for efficient water treatment - Qianqian Zeng; Zhiyu Zhao; Yue Wang; Siyuan Chen; Hua Li; Cheng Chen; Wei Yu; Jiaheng Teng; Hongjun Lin; Yu Yang; Liguo Shen (Chemical Engineering Journal, 2025)

Perhydroxylated benzoquinoid covalent triazine framework for ultra-high-density lithium-ion storage - Nhu T.H. Luu; Rajeshkumar Anbazhagan; Alexander S. Ivanov; Sung-En Lin; Chia-Hsin Chang; Chen-Yu Hung; Ilja Popovs; Jui-Chin Lee; Teng-Hao Chen; Watchareeya Kaveevivitchai (Chemical Engineering Journal, 2025)

Multifunctional flexible multilayer pressure sensor for pressure sensing, energy harvesting and versatile applications - Fu-Rui Teng; Song Sun; Si-Chen Tan; Ying-Jie Ma; Yue Huang; Lin Zhu; Di Wu; Ai-Dong Li (Chemical Engineering Journal, 2025)

Relative effects of sacred forests and protected areas on forest conservation and structure in Japan - Jonathan Peereman; Masahiro Aiba; Teng‐Chiu Lin (Conservation Biology, 2025)
Sacred forests, found on all inhabited continents, are globally recognized for their biodiversity and conservation value and their role in cultural landscapes. Assessments of the effects of forest sacredness have mostly focused on small regions and are based on diverse methods. We used geographic information provided by the public and datasets derived from remote sensing to locate and examine changes in shrine and temple forests across Japan. We compared the aboveground vegetation structure and annual rate of forest loss of these sacred forests with their surrounding nonsacred forests and with legally protected areas. We tested whether these differences were comparable between urban and rural areas and between shrine and temple forests. Based on a sample of 35,899 sacred forests, sacred forests had higher canopy height (mean [SD] = 15.5 m [0.02] vs. 15.2 m [0.01], t test, p

Alisertib inhibits acute myeloid leukemia cell growth by inhibiting STAT3 activation - Pang-Ting Cheng; Ho Lin; Yu-Chiao Cheng; Tzu-Hung Hsiao; Pei-Pei Jhan; Jia-Rung Tsai; Mei-Chih Chen; Tai-Lin Chen; Chieh-Lin Jerry Teng (Toxicology and Applied Pharmacology, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Promoting new energy-powered agricultural machinery: A network game model approach - Li Ma; Jiahao Lin; Yun Teng (Journal of Cleaner Production, 2025)

Heteroatom- and bonded tailored Schottky barrier in Ti₃C₂ MXene/carbon nitride heterojunctions toward efficient photocatalysis - Weinan Xing; Huage Lin; Weifan Shao; Ning Jian; Teng Liu; Shanpeng Wen; Jiangang Han; Guangyu Wu (Chemical Engineering Journal, 2025)

Deciphering the nexus of soluble microbial products (SMPs) and membrane fouling: Roles, mechanisms, and control strategies - Xinyu Hu; Hongjun Lin; Genying Yu; Liguo Shen; Jiaheng Teng; Meijia Zhang; Bisheng Li; Leihong Zhao; Die ling Zhao; Cheng Chen (Chemical Engineering Journal, 2025)

Edge-electron induced ferrimagnetic effect to accelerate interfacial desolvation kinetics toward dendrite-free Zn metal batteries - Haifeng Yang; Fangqi Liu; Bixian Chen; Xiaomin Cheng; Qinghua Guan; Jing Dong; Teng Li; Lujie Jia; Wenbin Wang; Jing Zhang; Jiqiang Jia; Yongzheng Zhang; et al. (Chemical Engineering Journal, 2025)

Successional trajectories differ between soil microbial guilds after logging in mixed conifer-broadleaf forests - Qiuyan Tan; Xingwu Lin; Leho Tedersoo; Jiasui Li; Xiuhai Zhao; Jianguo Zhu; Haiyan Chu; Teng Yang (Plant and Soil, 2025)

Transcriptomic and Metabolomic Analyses Provide Insights into Cryptocaryon irritans Resistance in Golden Pompano (Trachinotus ovatus) - Bo Liu; Bao-Suo Liu; Jing-Wen Yang; Hua-Yang Guo; Nan Zhang; Teng-Fei Zhu; Lin Xian; Ke-Cheng Zhu; Dian-Chang Zhang (Fishes, 2025)
Golden pompano (Trachinotus ovatus) is an economically important fish species along China’s southern coast. However, infections by Cryptocaryon irritans severely constrain the healthy and sustainable development of the aquaculture industry. To investigate the genetic basis of resistance to this parasite in golden pompano, this study employed transcriptomic and metabolomic analyses to compare differences between susceptible (ES) and resistant (RS) groups following C. irritans challenge. Transcriptome analysis identified 2031 differentially expressed genes (DEGs) between EST and RST groups, comprising 1004 up-regulated and 1027 down-regulated genes. Gene Ontology (GO) functional annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment revealed that these DEGs were primarily enriched in lipid metabolism and amino acid metabolism pathways. Untargeted metabolomics detected 461 significantly differentially abundant metabolites (295 up-regulated, 166 down-regulated), confirming pronounced metabolic differences between ES and RS groups, particularly in lipid and amino acid metabolism. Further, KEGG enrichment highlighted steroid hormone biosynthesis, α-linolenic acid metabolism, and arachidonic acid metabolism as the most significantly altered pathways upon infection. This integrated transcriptomic and metabolomic study reveals substantial differences in gene expression and metabolite profiles between susceptible and resistant golden pompano in response to C. irritans. These changes predominantly involve lipid metabolism and amino acid metabolism, suggesting that these processes are critical in determining host resistance/susceptibility.

Bio-derived carboxymethyl cellulose-graft-gallic acid antiscalant with remarkable antibacterial activity for reverse osmosis scaling and biofouling control - Liping Xiong; Wei Yu; Chenglin Ji; Longyufan Liu; Jiaheng Teng; Cheng Chen; Hongjun Lin; Liguo Shen (Water Research, 2025)

Bipolar membrane electrodialysis for producing acid and alkali from concentrated seawater: Industrial application in Bohai Sea, China - Jia-Wang Qin; Shun Tang; Jia-Lin Shi; Teng-Fei Zhang; Lu Yang; Fang Wang; Liang Yin; Yuan-Fa Zhuang (Journal of Water Process Engineering, 2025)

Revolutionary photoelectrochemical water splitting performance of BiVO₄/Bi₂S₃ heterojunction photoanodes boosted by trace bio-Cr₂O₃ through multiple mechanisms - Yefei Su; Yang Yu; Tingting Xue; Kai Teng; Yuning Fan; Jiangjun Lin; Chang Liu; Qing Qu; Lei Li (Chemical Engineering Journal, 2025)

Identifying Geochemical Anomalies Associated with Vanadium Mineralization in Jiujiang City (China) Using Convolutional Neural Network with Attention Mechanism - Zenghua Li; Yong Jiang; Yuheng Lin; Yongpeng Ouyang; Lili Wang; Lifei Yang; Youguo Deng; Teng Deng; Deru Xu (Natural Resources Research, 2025)

Impacts of forest fire on hydro-sediment using the SWAT model: a case study in the Zhangweinan Canal, China - Lin Qi; Xia Li; Yu Pan; Teng Yu (Acta Geophysica, 2025)

Astrocyte involvement in brain metastasis: from biological mechanisms to therapeutic strategies - Teng Zhou; Yuxin Yan; Mingxi Lin; Cheng Zeng; Xinhui Mao; Yifei Zhu; Jinlu Han; Dou-Dou Li; Jian Zhang (Cancer and Metastasis Reviews, 2025)

Effect of electron beam irradiation on the quality of chicken during post-mortem ageing - Xin Wang; Linya Wang; Jiangtao Yu; Yifeng Teng; Xiaomei Xiang; Dan Zhang; Luyao Kang; Yabin Niu; Xianchao Feng; Lin Chen (Food Chemistry, 2025)

Transient receptor potential vanilloid-1 (TRPV1) is a mediator of noise-induced neural damage in zebrafish and mice - Ruicun Liu; Boyu Luo; Honglu Yan; Qing Lin; Wei Liu; Xiaowei Hao; Shuai Huang; Zhenjun Luo; Tuoyu Liu; Jinyu Li; Zhiyuan Shi; Songzuo Liu; et al. (Science China Life Sciences, 2025)

ROS acted as an initial role in selenium nanoparticles alleviating insecticide chlorpyrifos-induced oxidative stress, pyroptosis, and intestinal barrier dysfunction in porcine intestinal epithelial cells - Minna Qiu; Zhiyu Hao; Yuhao Liu; Yuhang Liu; Minghang Chang; Xu Lin; Xiumei Liu; Na Dong; Wei Sun; Xiaohua Teng (Pesticide Biochemistry and Physiology, 2025)

Gut microbiota and metabolic functions in herbivorous fish from Xisha coral reefs, China - Xiyue Yang; Yayuan Xiao; Xiaojun Shi; Tuanjie Li; Xiaofei Xiong; Teng Wang; Lin Lin; Yu Liu; Jian Zou; Chunhou Li; Yong Liu; Peng Wu (Marine Environmental Research, 2025)

Association of prenatal exposure to perfluoroalkyl and polyfluoroalkyl substances with fetal growth trajectories - Yi Yang; Sheng Teng; Leshi Lin; Wenjuan Li; Zhenzhen Zhu; Tangxin Chen; Li Li; Fang Peng; Dongmei Peng; Xiao Gao (Environmental Research, 2025)

Pollution risk assessment and source apportionment of potentially toxic elements in agricultural soils using the APCS-MLR model: a case study near a non-ferrous metal smelting slag site in Gejiu, Yunnan - Chao-liang Peng; Zhe Wang; Ying Luo; Jia-Qian Zhang; Zhen-Long Zhang; Yi-ming Chen; Kai Ye; Wen-xue Lin; Jing-yan Zhang; Teng-jiao Xie (Environmental Monitoring and Assessment, 2025)

eDNA Metabarcoding Reveals the Depth-Structured Variation of Coral Reef Fish - Jinfa Zhao; Lin Lin; Yong Liu; Teng Wang; Yu Liu; Yayuan Xiao; Jianzhong Shen; Hongyu Xie; Hai Huang; Qiuying Han (Fishes, 2025)
Global coral reef ecosystems face various levels of disturbance pressure. Understanding the depth-structured variation in coral reef fish communities can help us to better grasp and predict the adaptive changes of the ecosystem under different stressors. This study applied eDNA metabarcoding technology to analyze the spatial distribution of the coral reef fish at various depths (0 m, 5 m, 10 m, 15 m, 20 m, 30 m, 40 m, 50 m, and 60 m) within the Xisha Islands of China. The results indicated that the eDNA technology detected a total of 213 amplicon sequence variants (ASVs), including 33 species that were not identified using traditional methods. Herbivorous fish generally dominated in relative abundance across different depths. Moreover, the similarity among depth groups was largely absent, and significant differences existed in fish assemblages across depth gradients, consistent with the unique depth preferences of fish microhabitats. Importantly, our findings revealed distinct depth-structured variation among different functional groups of coral reef fish. Large carnivorous fish initially increased and then decreased along the depth gradient from 0 to 60 m, with a turning point around 20 m, while large herbivorous fish displayed the opposite trend. Small carnivorous and small herbivorous fish consistently declined along the same depth gradient. Additionally, the Margalef index (D) and Function richness (FRic) both displayed a consistent downward trend with increasing depth, while the Shannon–Wiener index (H′), Pielou index (J′), Quadratic entropy (RaoQ), Functional dispersion (FDis), and Functional evenness (FEve) initially increased and then decreased, peaking around 20 m. This study revealed that eDNA metabarcoding is an effective tool for evaluating coral reef fish biodiversity, community composition, and spatial distribution. It enhances our understanding of distribution dynamics and offers valuable insights for coral reef conservation and restoration efforts.

A synergistic approach integrating potassium ferrate oxidation with polyacrylamide flocculation to enhance sludge dewatering and its mechanisms - Yansha Zeng; Yue Shen; Hongjun Lin; Qiyin Tan; Jiahao Sun; Liguo Shen; Renjie Li; Yanchao Xu; Jiaheng Teng (Journal of Environmental Management, 2025)

Molecular mechanisms based on peripheral level of vanillin recognition in Orthaga achatina (Lepidoptera: Pyralidae) - Ting-Ting Yang; Yu Ma; Zheng Dai; Ying Li; Ji-Xiang Wang; Teng-Fei Bai; Merid Negash Getahun; George F.O. Obiero; Shuang-Lin Dong; Jin Zhang; Qi Yan (Insect Biochemistry and Molecular Biology, 2025)

Novel Perspectives Focused on the Relationship Between Herpesvirus Encephalitis and Anti-GFAP-Antibody-Positive Astrocytopathy - Yuqiao Liao; Linxin Wen; Ruoyi Zheng; Yinan Shen; Teng-Ai Ha; Mingkai Lin; Ruogu Cheng; Ye Gao; Pei Shang (Molecular Neurobiology, 2025)

Methamphetamine and HIV-1 Tat Protein Synergistically Induce Endoplasmic Reticulum Stress to Promote TRIM13-Mediated Neuronal Autophagy - Chan Wang; Genmeng Yang; Jian Huang; Yunqing Tian; Chi-Kwan Leung; Lin Miao; Haowei Wang; Yi Li; Yizhen Huang; Hanxin Teng; Liu Liu; Juan Li; et al. (Molecular Neurobiology, 2025)

Synergistic Regulation of Color Transformation by Nutrient Elements, Osmotic Regulators, and Antioxidant Enzymes in Erythrophleum fordii - Zi-Long Ouyang; Xiang-Lu Jia; Tian-dao Bai; Lin-juan Huang; Xuan Jiang; Wei-Chao Teng (Journal of Plant Growth Regulation, 2025)

The consequence distance of liquid ammonia release from a pipeline in complex terrain - Lin Teng; Kangkang Wang; Bin Liu; Weidong Li; Pengbo Yin; Zhenchao Li; Xin Huang; Yu Luo; Lilong Jiang (Process Safety and Environmental Protection, 2025)

An integrated approach for spatio-temporal assessment and attribution of water resources carrying capacity: Incorporating AHP, TOPSIS, and lorenz asymmetry coefficient methods - Ting Zhou; Teng Lin; Rongliang Cheng; Guoqing Wang; Bo Jiang (Journal of Hydrology, 2025)

Linoleic acid alleviates aluminum toxicity by modulating fatty acid composition and redox homeostasis in wheat (Triticum aestivum) seedlings - Yiqun Ou; Zhuoran Teng; Yuchen Shu; Yi Wang; Dan Wang; Chengliang Sun; Xianyong Lin (Journal of Hazardous Materials, 2025)

Glycerol-driven optimization of algae-bacteria symbiosis systems for enhanced lipid production and self-flocculation - Yuwei Zhang; Jiaheng Teng; Jiahui Huang; Liguo Shen; Hongjun Lin; Renjie Li; Xiang Cai; Zeqiong Xu; Meijia Zhang (Journal of Environmental Chemical Engineering, 2025)

The Role and Mechanism of TRIM13 Regulation of TRAF6 Ubiquitination in the Synergy of Inflammatory Responses and Neurotoxicity Induced by METH and HIV- 1 Tat Protein in Astrocytes - Yi Tan; Lin Miao; Chan Wang; Haowei Wang; Yi Li; Yizhen Huang; Hanxin Teng; Yunqing Tian; Genmeng Yang; Xiaofeng Zeng; Juan Li (Neurotoxicity Research, 2025)

Causes and Geomorphological Effects of Relative Sea Level Movement in the Yellow River Delta During the Last 2000 Years - Qing Wang; Chao Zhan; Teng Su; Hongyuan Shi; Longsheng Wang; Lin Zeng; Xianbin Liu; Buli Cui (Journal of Ocean University of China, 2025)

Gut microbiome composition likely affects the growth of Trachinotus ovatus by influencing the host's metabolism - Chen-Xu Wu; Bao-Suo Liu; Hua-Yang Guo; Teng-Fei Zhu; Lin Xian; Nan Zhang; Ke-Cheng Zhu; Dian-Chang Zhang (Aquaculture International, 2025)

Effect of cultivar and process on the astringency of matcha based on flavonoids-targeted metabolomic analysis - Jinjin Xue; Panpan Liu; Yongquan Xu; Anhui Gui; Xueping Wang; Fei Ye; Lin Feng; Shengpeng Wang; Jing Teng; Shiwei Gao; Pengcheng Zheng (Food Research International, 2025)

Exploration of the regulatory mechanism of pulsed electric field on the aggregation behavior of soybean protein isolates - Rui Wang; Pei-Feng Guo; Jin-Peng Yang; Yan-Yan Huang; Lang-Hong Wang; Jian Li; Song-Yi Lin; Qing-Lin Sheng; Xin-An Zeng; Yong-Xin Teng (Food Hydrocolloids, 2025)

Spatiotemporal correlations of PM2.5 and O3 variations: A street-scale perspective on synergistic regulation - Xinyuan Lin; Yangbin Dong; Zuying Teng; Zhaocai Meng; Fuwang Zhang; Xisheng Hu; Zhanyong Wang (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Global Epidemiology and health risks of Bacillus cereus Infections: Special focus on infant foods - Na Li; Abubakar Siddique; Ningjun Liu; Lin Teng; Abdelaziz Ed-Dra; Min Yue; Yan Li (Food Research International, 2025)

Biological Traits of Spodoptera litura (Fabricius) in Response to Joint Application of Beauveria bassiana (Balsamo)Vuillemin and Emamectin Benzoate - Jiaying Li; Qingsong Cheng; Lin Chen; Kai Teng; Weiai Zeng; Hailin Cai; Shen Zhang; Zhipeng Xiao; Shaolong Wu; Bin Hu; Zhenxing Zhao; Hongwu Yang; et al. (Journal of Crop Health, 2025)

The dominance of K-strategy microbes enhances the potential of soil carbon decomposition under long-term warming - Yanli Gao; Jiacong Zhou; Teng-chiu Lin; Yiqing Li; Quanxin Zeng; Shidong Chen; Decheng Xiong; Qiufang Zhang; Zhijie Yang; Yusheng Yang (Applied Soil Ecology, 2025)

Role of C/EBP Homologous Protein in Vascular Stenosis After Carotid Artery Injury - Lin Teng; Qin Qin; Zi-yi Zhou; Fei Zhou; Cun-yu Cao; Chao He; Jia-wang Ding; Jian Yang (Biochemical Genetics, 2025)

Innovative targeted protection of lactoferrin enriched whey increased the immunoactivity of infant formula - Qiaran Lin; Yue Wang; Yizhe Teng; Baoxin Gu; Lina Zhang; Peng Zhou (Food Bioscience, 2025)

Improved viability of probiotics by co-encapsulation of wheat germ oil under storage and gastrointestinal conditions: Effects of drying methods and wall composition - Bao-Lin He; Rui Cui; Teng-Gen Hu; Hong Wu (Food Hydrocolloids, 2025)

SNPs in the Galectin-8 gene of Acanthopagrus latus have been found to be associated with resistance trait to Streptococcus iniae - Jin-Min Pan; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Lin Xian; Teng-Fei Zhu; Ke-Cheng Zhu; Dian-Chang Zhang (Aquaculture International, 2025)

Detection of Tetracycline in Farm Wastewater by Nitrogen-doped Carbon Quantum Dots - Peilan Yu; Lintong Ji; Teng Wang; Juan Hu; Lihao Jiang; Shancai Guo; Yongjian Pan; Jianyuan Lin (Journal of Fluorescence, 2024)

A survey on evaluation of blockchain-based agricultural traceability - Shaoning Pang; Shyh Wei Teng; Manzur Murshed; Cuong Van Bui; Priyabrata Karmakar; Yanyu Li; Hao Lin (Computers and Electronics in Agriculture, 2024)

Characterization of the Galectin-3 gene and its association with Streptococcus iniae resistance traits in Acanthopagrus latus (Houttuyn, 1782) - Jin-Min Pan; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Lin Xian; Teng-Fei Zhu; Ke-Cheng Zhu; Dian-Chang Zhang (Aquaculture, 2024)

Potato Protein Hydrolysate (PPH902) treatment in adipocytes inhibits lipogenesis by activating AMPK - Yi-Ju Chen; Ching-Fang Chang; Rathinasamy Baskaran; Chih-Hung Liang; Hsin-Ning Kuo; Mosleh Mohammad Abomughaid; Wan-Teng Lin (South African Journal of Botany, 2024)

Membrane fouling mechanisms in the presence of microplastics and organic matter: The unexpected mitigating role of Ca2+ - Xiaoni Zhou; Wenfa Yang; Hongjun Lin; Biyan Wang; Mingjing Xie; Hao Fang; Hanmin Zhang; Meijia Zhang; Jiaheng Teng (Science of The Total Environment, 2024)

Western diet induces GSDME-mediated epithelial pyroptosis through the DCA-S1PR2 pathway to disrupt the intestinal epithelial barrier - Ke Liu; Mengyao Song; Xueqin Huang; Yanqiang Shi; Sheng Li; Fangqing Zhu; Teng Ben; Xinlong Lin; Bingxia Chen; Beibei Xu; Sicong Ma; Binhai Shen; et al. (Science Bulletin, 2024)

Urban surface-emitted longwave radiation estimation from high spatial resolution thermal infrared images using a hybrid method - Songyi Lin; Huazhong Ren; Rongyuan Liu; Jinxiang Li; Shanshan Chen; Yuanjian Teng; Wenjie Fan; Baozhen Wang; Yu Liu (Remote Sensing of Environment, 2024)

Effect of steady boundary-layer flow on the hydrodynamic forces on a near-wall cylinder in currents - Yunfei Teng; Terry Griffiths; Liang Cheng; Yan Qu; Hongwei An; Scott Draper; Zhe Gao; Guoqiang Tang; Lin Lu (Ocean Engineering, 2024)

Excellent antibiotic degradation through PMS activation via bio derived Fe-Mn oxides with tunable defect concentration: Synergy between singlet oxygen oxidation and electron transfer - Kai Teng; Jiajie Wu; Yuxi Chen; Lin Ge; Guang Li; Yuning Fan; Qing Qu; Lei Li (Journal of Environmental Chemical Engineering, 2024)

A modified self-micro emulsifying liposome for bioavailability enhancement of quercetin and its biological effects - S.Y. Lin; T.T. Chen; Mohamed A. Farag; H. Teng; H. Cao (Food Bioscience, 2024)

The roles of organic amendments and plant treatments in soil polychlorinated biphenyl dissipation under oxic and sequential anoxic–oxic conditions - Meng Yan; Tingting Peng; Ling Zhao; Qigang Li; Ruini Wu; Yiming Wang; Yucheng Wu; Ying Teng; Xingjia Xiang; Jun Zeng; Xiangui Lin (Environmental Research, 2024)

Diurnal and seasonal carbon budget of subtropical moss-dominated biocrusts - Ye Ji; Xiangping Su; Teng-Chiu Lin; Xiaofei Liu; Decheng Xiong; Chao Xu; Shidong Chen; Zhijie Yang; Yusheng Yang (Plant and Soil, 2024)

SLC10A1 rs2296651 variant (S267F mutation) predicts biochemical traits, hepatitis B virus infection susceptibility and the risk of gallstone disease - Yu-Lin Ko; Wei-Lun Tuan; Ming-Sheng Teng; Wei-Chih Su; Chia‑Chi Wang; Leay-Kiaw Er; Semon Wu; Lung-An Hsu (Molecular Genetics and Genomics, 2024)

Circ-Luc7l Absence Attenuates Diabetic Nephropathy Progression by Reducing Mesangial Cell Excessive Proliferation, Inflammation, and Extracellular Matrix Accumulation via Mediating the miR-205-5p/Tgfbr1 Pathway - Zhan Fang; Dan Wang; Fang Sun; Jing Chang; Dong Yuan; Shuhua Lin; Jian Teng (Biochemical Genetics, 2024)

A detailed analysis of 16S rRNA gene sequencing and conventional PCR-based testing for the diagnosis of bacterial pathogens and discovery of novel bacteria - Mei-Na Li; Ting Wang; Nan Wang; Qiang Han; Xue-Ming You; Shuai Zhang; Cui-Cui Zhang; Yong-Qiang Shi; Pei-Zhuang Qiao; Cheng-Lian Man; Teng Feng; Yue-Yue Li; et al. (Antonie van Leeuwenhoek, 2024)

Validation of the constitution in Chinese medicine questionnaires with the newly developed blood-vacuity category: a rare Taiwanese case study - Ting-Yu Huang; Shi-Chen Ou; Wei-Te Huang; Yu-Chuan Lin; Hao-Hsiu Hung; Chin-Wei Chang; Kai-Yuan Hsiao; Yi-Wei Kao; Chien-Hua Wu; Wei-Shan Chang; Ben-Chang Shia; Sheng-Teng Huang (Advances in Traditional Medicine, 2024)

Root physiological and morphology processes co-regulate the growth of Chinese-fir saplings in response to warming and precipitation reduction in the sub-tropical regions - Decheng Xiong; Jinxue Huang; Xulong Du; Teng-chiu Lin; Yuanhao Liu; Shidong Chen; Xiaofei Liu; Chao Xu; Zhijie Yang; Yusheng Yang (Forest Ecology and Management, 2024)

Optimization of microalgal-bacterial consortium flocculation through chitosan-diatomite composite materials: A sustainable approach to biomass harvesting - Yu Zhao; Qian Lei; Jiaheng Teng; Xiu Zhang; Hongjun Lin; Meijia Zhang (Chemical Engineering Journal, 2024)

Gel electrolyte design for nonflammable lithium-ion batteries with high-rate and high-voltage characteristics - Po-Wei Huang; Qin-Cheng Zhang; Ming-Yuan Hung; Yan-Cheng Lin; Hong-Kang Tian; Yuh-Lang Lee; Jeng-Shiung Jan; Hsisheng Teng (Chemical Engineering Journal, 2024)

Homeostatic nanomedicine: Protein S-nitrosylation dyshomeostasis dominated oncotherapy based on a tumor-microenvironment-activated nanoparticle - Xiaowen Cai; Junming Li; Ruoqi Zhang; Jie Zhou; Hongmiao Lin; Xiaohua Huang; Chuanshan Xu; Yanli Li; Teng Gong (Chemical Engineering Journal, 2024)

Ultra-Low-Dose UV-C Photo-stimulation Promotes Neural Stem Cells Differentiation via Presenilin 1 Mediated Notch and β-Catenin Activation - Lin Zhou; Zihan Wang; Qiuling Zhong; Bing Song; Yan Wang; Teng Guan; Qian Liu (Molecular Neurobiology, 2024)

The effect of cross-regional transport on ozone and particulate matter pollution in China: A review of methodology and current knowledge - Kun Qu; Yu Yan; Xuesong Wang; Xipeng Jin; Mihalis Vrekoussis; Maria Kanakidou; Guy P. Brasseur; Tingkun Lin; Teng Xiao; Xuhui Cai; Limin Zeng; Yuanhang Zhang (Science of The Total Environment, 2024)

In vivo detection of endogenous toxic phenolic compounds of intestine - Wen-Yu Jin; Jia-Xin Guo; Rongkang Tang; Jielin Wang; Huan Zhao; Meng Zhang; Lin-Zuo Teng; Philippe J. Sansonetti; Yi-Zhou Gao (Journal of Hazardous Materials, 2024)

Unraveling the mechanism of selective dissolution in anthracite coal for enhanced permeability through sodium hypochlorite oxidation treatment - Yu Lu; Yili Kang; Zhigang Li; Ming Yue; Teng Zhang; Feng He; Chong Lin; Yue Hu; Ying Li; Zhenjiang You (Fuel, 2024)

Molecular characterization of histone gene in golden pompano (Trachinotus ovatus) and antimicrobial activity of its derived peptides - Yu Liang; Jin-Min Pan; Ke-Cheng Zhu; Lin Xian; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Teng-Fei Zhu; Dian-Chang Zhang (Fish & Shellfish Immunology, 2024)

Strong absorption of silica over full solar spectrum boosted by interfacial junctions and light–heat–storage of Mg(OH)2–(CrOx–SiO2) - Rui-Min Hao; Lin Zhu; Teng-Fei Shang; Zhi-Bin Xu; Qin-Pei Wu (Chemical Engineering Journal, 2024)

Prediction of stability of a slope with weak layers using convolutional neural networks - Mansheng Lin; Limei Zeng; Shuai Teng; Gongfa Chen; Bo Hu (Natural Hazards, 2024)

The GLCCI1/STAT3 pathway: a novel pathway involved in diabetic cognitive dysfunction and the therapeutic effect of salidroside - Lin Niu; Min Xu; Wenqiang Liu; Hongdan Yu; Shengxue Yu; Fuzhi Li; Teng Wang; Die Sun; Tiefeng Yao; Wanze Li; Zhengzhong Yang; Xuezheng Liu; et al. (Journal of Molecular Histology, 2024)

Estimating river discharge across scales with a novel regional gauging method driven by Sentinel satellite data - Hong Lin; Xiao Cheng; Junguo Liu; Qian Shi; Teng Li; Lei Zheng; Xuejiao Hou; Jinyang Du (Remote Sensing of Environment, 2024)

Combination of an enzyme-linked immunosorbent assay and an indirect fluorescence assay for a nationwide sero-survey of Toxoplasma gondii infection in pig herds in Taiwan - Kendy Tzu-Yun Teng; Chao-Chin Chang; Shao-Wen Hung; Ming-Tang Chiou; Chao-Nan Lin; Cheng-Yao Yang (Preventive Veterinary Medicine, 2024)

A synergistic approach combining computational fluid dynamics simulation with hydrolysis-acidification for dye wastewater treatment - Zhe Wang; Yansha Zeng; Zhenxiang Pan; Liguo Shen; Bizhen Zeng; Jiaheng Teng; Hongjun Lin (Journal of Environmental Management, 2024)

Assessing the degree of impact from iceberg activities on penguin colonies of Clarence Island - Hong Lin; Xiao Cheng; Teng Li; Qian Shi; Qi Liang; Xinyu Meng; Shaoyin Wang; Lei Zheng (Acta Oceanologica Sinica, 2024)

Neonicotinoids as emerging contaminants in China’s environment: a review of current data - Lingzhi Liao; Ting Sun; Zhenhui Gao; Jianing Lin; Meng Gao; Ao Li; Teng Gao; Ziqin Gao (Environmental Science and Pollution Research, 2024)

Molecular mechanism of apoptosis induced by 4-tBP in common carp (Cyprinus carpio L.) head kidneys was explored from various angles: Hippo pathway, miR-203a, oxidative stress, ER stress, and mitochondrial pathway - Jiatian Liang; Xu Lin; Chunyu Jiang; Yuhao Liu; Zhiyu Hao; Minna Qiu; Xiumei Liu; Dechun Chen; Xiaohua Teng; You Tang (Aquaculture, 2024)

Genomic analysis of Alteromonas sp. M12 isolated from the Mariana Trench reveals its role in dimethylsulfoniopropionate cycling - Yue Lin; Min Zhang; Yu-Xiang Lai; Teng Liu; Meng Meng; Yan Sun; Yu Wang; Qing-Yu Dong; Chen-Xi Li; Meng-Xue Yu; Jin Cheng; Shu-Jun Liu; et al. (Marine Genomics, 2024)

Enhanced sludge dewatering using a novel synergistic iron/peroxymonosulfate-polyacrylamide method - Yansha Zeng; Zhe Wang; Qiyin Tan; Yue Shen; Jiahao Sun; Liguo Shen; Jiaheng Teng; Hongjun Lin (Journal of Environmental Management, 2024)

Predicting thermodynamic adhesion energies of membrane fouling in planktonic anammox MBR via backpropagation neural network model - Xiang Cai; Si Pang; Meijia Zhang; Jiaheng Teng; Hongjun Lin; Siqing Xia (Bioresource Technology, 2024)

Feasibility studies in applying cork to pile-type two-layered seismic metamaterials - Tung-Yu Wu; Wei-Lin Teng; Hsiang-Hao Hsieh; Shiang-Jung Wang; Kuo-Chun Chang (Soil Dynamics and Earthquake Engineering, 2024)

A systematic study on the chemical model of polycyclic aromatic hydrocarbons formation from nutrients (glucose, amino acids, fatty acids) in food - Qiuyi Lin; Haolin Zhang; Xiaomei Lv; Ruiwei Xie; Bing-Huei Chen; Yu-Wen Lai; Lei Chen; Hui Teng; Hui Cao (Food Chemistry, 2024)

Co-delivery of indomethacin and uricase as a new strategy for inflammatory diseases associated with high uric acid - Jie Liu; Chenshi Lin; Man Wu; Yingjie Wang; Shenyu Chen; Taiwang Yang; Chenlu Xie; Yue Kong; Wenliang Wu; Jiaping Wang; Xiaonan Ma; Chao Teng (Drug Delivery and Translational Research, 2024)

Innovative treatment of industrial effluents through combining ferric iron and attapulgite application - Zhenxiang Pan; Bizhen Zeng; Liguo Shen; Jiaheng Teng; Tongli Lai; Leihong Zhao; Genying Yu; Hongjun Lin (Chemosphere, 2024)

First fossil pod of Mezoneuron (Caesalpinioideae, Fabaceae) in Asia - Yi-Shan Zhao; Teng-Xiang Wang; Lin-Bo Jia; Ai Song; Jian Huang; Tao Su (Review of Palaeobotany and Palynology, 2024)

Effects of air warming and soil warming on ecophysiological processes of leaves and fine roots of Cunninghamia lanceolata saplings - Xulong Du; Jinxue Huang; Decheng Xiong; Zhijie Yang; Teng-chiu Lin; Shidong Chen; Xiaofei Liu; Chao Xu; Yusheng Yang (Forest Ecology and Management, 2024)

Engineered delivery platform based on bacterial outer membrane vesicles for efficient labeling of 131I and improved radio-immunotherapy - Haidong Shen; Surui Chen; Chonghai Zhang; Teng Liu; Yugui Tao; Lin Hu; Kai Yang (Chemical Engineering Journal, 2024)

PLD2 deletion ameliorates sepsis-induced cardiomyopathy by suppressing cardiomyocyte pyroptosis via the NLRP3/caspase 1/GSDMD pathway - Jun Li; Da Teng; Wenjuan Jia; Lei Gong; Haibin Dong; Chunxiao Wang; Lihui Zhang; Bowen Xu; Wenlong Wang; Lin Zhong; Jianxun Wang; Jun Yang (Inflammation Research, 2024)
Objective Sepsis-induced cardiomyopathy (SICM) is a life-threatening complication. Phospholipase D2 (PLD2) is crucial in mediating inflammatory reactions and is associated with the prognosis of patients with sepsis. Whether PLD2 is involved in the pathophysiology of SICM remains unknown. This study aimed to investigate the effect of PLD2 knockout on SICM and to explore potential mechanisms. Methods The SICM model was established using cecal ligation and puncture in wild-type and PLD2-knockout mice and lipopolysaccharide (LPS)-induced H9C2 cardiomyocytes. Transfection with PLD2-shRNA lentivirus and a PLD2 overexpression plasmid were used to interfere with PLD2 expression in H9C2 cells. Cardiac pathological alterations, cardiac function, markers of myocardial injury, and inflammatory factors were used to evaluate the SICM model. The expression of pyroptosis-related proteins (NLRP3, cleaved caspase 1, and GSDMD-N) was assessed using western blotting, immunofluorescence, and immunohistochemistry. Results SICM mice had myocardial tissue damage, increased inflammatory response, and impaired heart function, accompanied by elevated PLD2 expression. PLD2 deletion improved cardiac histological changes, mitigated cTNI production, and enhanced the survival of the SICM mice. Compared with controls, PLD2-knockdown H9C2 exhibits a decrease in inflammatory markers and lactate dehydrogenase production, and scanning electron microscopy results suggest that pyroptosis may be involved. The overexpression of PLD2 increased the expression of NLRP3 in cardiomyocytes. In addition, PLD2 deletion decreased the expression of pyroptosis-related proteins in SICM mice and LPS-induced H9C2 cells. Conclusion PLD2 deletion is involved in SICM pathogenesis and is associated with the inhibition of the myocardial inflammatory response and pyroptosis through the NLRP3/caspase 1/GSDMD pathway.

Effect of High Magnesium and Astragaloside IV on Vascular Endothelial Cells - Hongfei Qi; Teng Ge; Kun Wang; Jing Wang; Lin Dang; Juane Li; Haifang Wang (Cell Biochemistry and Biophysics, 2024)

An efficient solution based on the synergistic effects of nickel foam in NiFe-LDH nanosheets for oil/water separation - Xinchun Lu; Liguo Shen; Hongjun Lin; Lei Han; Jiarong Du; Cheng Chen; Jiaheng Teng; Bisheng Li; Wei Yu; Yanchao Xu (Journal of Hazardous Materials, 2024)

Maize stem–leaf segmentation framework based on deformable point clouds - Xin Yang; Teng Miao; Xueying Tian; Dabao Wang; Jianxiang Zhao; Lili Lin; Chao Zhu; Tao Yang; Tongyu Xu (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Microcystin-RR promote lipid accumulation through CD36 mediated signal pathway and fatty acid uptake in HepG2 cells - Wenjuan Jia; Lin Zhong; Qingmiao Ren; Da Teng; Lei Gong; Haibin Dong; Jun Li; Chunxiao Wang; Yong-Xing He; Jun Yang (Environmental Research, 2024)

Synergistic disparities of pollution reduction and carbon mitigation in the industrial chain: Evidence from China's industrial sector - Boqiang Lin; Yuqiang Teng (Environmental Research, 2024)

Therapeutic strategies for small-diameter vascular graft calcification - Yanjiao Teng; Yang Xu; Pengfei Lv; Lin Song; Jianing Yang; Xiudan Wang; Xiaoqin Guo; Shufang Wang; Shike Hou; Qi Lv; Jie Shi (Chemical Engineering Journal, 2024)

Distribution Patterns of Grey Mullet in the Taiwan Strait in Relation to Oceanographic Conditions - Sheng-Yuan Teng; Sandipan Mondal; Quang-Huy Lu; Platinasoka Lin; Ming-An Lee; Louis George Korowi (Journal of Marine Science and Engineering, 2024)
The depletion of the grey mullet population in the Taiwan Strait has generated interest in conservation initiatives and to enhance the effectiveness of restoration initiatives, it is essential to comprehend the specific habitat preferences of the species in question, particularly in relation to environmental changes. In this study, habitat suitability modelling was used to investigate the distribution patterns of grey mullet. Sea surface height (SSH) was the most significant predictor of the grey mullet standardized catch per unit effort (S.CPUE). Furthermore, sea surface temperature (SST) was the second most important oceanographic parameter, followed by mixed-layer depth (MLD). The grey mullet S.CPUE peaked in regions with the summed SST, Chla, salinity, SSH, MLD and current values being 20 °C, 0.9 mg/m3, 34.5 psu, 0.45 m, 18–38 m, and 0.25 m2/s2, respectively. From late October, HSI levels in the northern Taiwan ocean increased, with a consistent upward trend. The distribution expanded in November and December, focusing on the northern and mid-ocean regions west of Taiwan. HSI levels peak in January and February, especially in Taiwan’s coastal region. High HSI distribution shifts away from coastlines and diminishes in April. The findings of this study will contribute to the understanding of this specific species and the approach used in this study may be applicable to other fisheries stocks also.

Dinaciclib inhibits the growth of acute myeloid leukemia cells through either cell cycle-related or ERK1/STAT3/MYC pathways - Chieh-Lin Jerry Teng; Pang-Ting Cheng; Yu-Chiao Cheng; Jia-Rung Tsai; Mei-Chih Chen; Ho Lin (Toxicology in Vitro, 2024)

Mg2+ addition: Unlocking optimized treatment performance and anti-fouling property in microalgal-bacterial membrane bioreactors - Fei Huang; Yu Zhao; Shilei Chen; Hongjun Lin; Jiaheng Teng; Xiang Cai; Meijia Zhang (Science of The Total Environment, 2024)

Constructed wetland treating mine drainage wastewater: Performance and microbial mechanisms - Xiaoyong Zhong; Xindong Teng; Bo Tang; Xunan Lin; Junbin Chen; Ronghua Zhao; Qiang Wu; Xiao Huang (Journal of Water Process Engineering, 2024)

Advances in synthesis and application of amphoteric polymer-based water treatment agents - Wei Yu; Liping Xiong; Jiaheng Teng; Cheng Chen; Bisheng Li; Leihong Zhao; Hongjun Lin; Liguo Shen (Desalination, 2024)

Microbiological hazards in infant and toddler food in China: A comprehensive study between 2004 and 2022 - Lin Teng; Linlin Huang; Haiyang Zhou; Baikui Wang; Min Yue; Yan Li (Food Research International, 2024)

Corrigendum to “Serviceability evaluation of highway tunnels based on data mining and machine learning: A case study of continental United States” [Tunnelling and Underground Space Technology 142 (2023) 105418] - Ya-Dong Xue; Wei Zhang; Yi-Lin Wang; Wei Luo; Fei Jia; Sheng-Teng Li; Hao-Jun Pang (Tunnelling and Underground Space Technology, 2024)

Harnessing diurnal dynamics: Deciphering the interplay of light cycles on algal-bacterial membrane bioreactors - Sihan Cheng; Yuwei Zhang; Yu Zhao; Xin Hu; Hongjun Lin; Jiaheng Teng; Meijia Zhang (Science of The Total Environment, 2024)

Role of residential greenspace in the trajectory of major neurological disorders: A longitudinal study in UK Biobank - Xin Hu; Jiawei Wang; Teng Yang; Jianbo Jin; Qiang Zeng; Omid Aboubakri; Xing Lin Feng; Guoxing Li; Jing Huang (Science of The Total Environment, 2024)

Controlling toxic Microcystis blooms: The power of a novel microalgal predator Poteriospumella lacustris in water safety improvement - Shuangshuang Chen; Wanxin Xie; Xu Lin; Hui Zhou; Siqi Teng; Zihan Jiang; Luming Yao; Hong Xu (Journal of Cleaner Production, 2024)

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

The energy-saving effect of industrial chain synergistic division: Evidence from China's industrial chain - Yuqiang Teng; Boqiang Lin (Energy Policy, 2024)

Mechanochemical synthesis of Ni/MgO dual functional materials at room temperature for CO2 capture and methanation - Zhan-Kuo Guo; Su Gao; Shu-Xiang Xiang; Jin-Peng Wang; Guo-Cui Mao; Hui-Lin Jiang; Bao-Xia Dong; Yun-Lei Teng (Chemical Engineering Journal, 2024)

BioTreasury: a community-based repository enabling indexing and rating of bioinformatics tools - Qi Zhao; Xin Zhou; Jingxing Wu; Jieyi Cai; Xiaoqiong Bao; Lin Tang; Chaoye Wang; Chunlei Liu; Yukai Wang; Yuyan Teng; Mohan Zheng; Weiping Mu; et al. (Science China Life Sciences, 2024)

Response of erosion-induced carbon loss to rainfall characteristics is forest type dependent - Xiangping Su; Chao Xu; Teng-Chiu Lin; Zhijie Yang; Xiaofei Liu; Shidong Chen; Decheng Xiong; Yusheng Yang (Agricultural and Forest Meteorology, 2024)

Co-infections of Aeromonas dhakensis and Chryseobacterium indologenes in largemouth bass (Micropterus salmoides) - Qin Yang; Yun-Yao Tu; Na Zhang; Bo Miao; Yu-Zhou Zhang; Xun-Teng Deng; Tao He; Sheng-Qi Su; Ling-Yun Lin; Song Zhu (Aquaculture, 2024)

Integrating photovoltaic noise barriers and electric vehicle charging stations for sustainable city transportation - Kai Zhang; Min Chen; Rui Zhu; Fan Zhang; Teng Zhong; Jian Lin; Linlin You; Guonian Lü; Jinyue Yan (Sustainable Cities and Society, 2024)

Sediment nitrates reduction processes affected by non-native Sonneratia apetala plantation in South China - Zhenzhen Teng; Xianbiao Lin (Science of The Total Environment, 2024)

Mxenes for membrane separation: from fabrication strategies to advanced applications - Zhengyi Huang; Die Ling Zhao; Liguo Shen; Hongjun Lin; Cheng Chen; Yanchao Xu; Bisheng Li; Jiaheng Teng; Lei Han; Tai-Shung Chung (Science Bulletin, 2024)

Crop monitoring by multimodal remote sensing: A review - Priyabrata Karmakar; Shyh Wei Teng; Manzur Murshed; Shaoning Pang; Yanyu Li; Hao Lin (Remote Sensing Applications: Society and Environment, 2024)

Overlooked fluorine deficiency in children of South and East China may be exacerbated by climate change: Evidence from the national assessment - Lingfeng Zhou; Weigang Liang; Yaobin Meng; Xiaoli Zhao; Fei Guo; Lingling Liu; Wenjing Li; Miaomiao Teng; Fanhao Song; Zhiqiang Cao; Yidong Mi; Qigen Lin; et al. (Journal of Cleaner Production, 2024)

Bacterial, short-chain fatty acid and gas profiles of partially hydrolyzed guar gum in vitro fermentation by human fecal microbiota - Xiong-E Pi; Hao Fu; Xiao-Xia Yang; Zai-Chun Yu; Wei-Lin Teng; Yinjun Zhang; Xue-Wei Ye; Hui Hui Quan; Li-Zhi Lu; Wei Liu (Food Chemistry, 2024)

4-Hydroxybenzenesulfonic acid triggers rapid preparation of phenolic aerogel composites by ambient pressure drying - Xi Zhao; Lin Chen; Peng-Gang Su; Lin-Xi Xiao; Hai-Bo Zhao; Teng Fu; Xiu-Li Wang; Yu-Zhong Wang (Chemical Engineering Journal, 2024)

Flexible metal membrane integrated electrified and catalytic attributes for multifunctional water purification with enhanced scaling resistance - Ning Kong; Liguo Shen; Qianqian Zeng; Cheng Chen; Jiaheng Teng; Feng Chen; Hongjun Lin (Chemical Engineering Journal, 2024)

Serviceability evaluation of highway tunnels based on data mining and machine learning: A case study of continental United States - Ya-Dong Xue; Wei Zhang; Yi-Lin Wang; Wei Luo; Fei Jia; Sheng-Teng Li; Hao-Jun Pang (Tunnelling and Underground Space Technology, 2023)

Two new ketene derivatives from the endophytic fungus Daldinia eschscholtzii J11 - Song-Mei Lu; Cheng-Juan Liao; Yuan Xu; Teng-Yuan Gui; He-Lin Sui; Min Zhou (Phytochemistry Letters, 2023)

Comparison of the environmental impact of typical packaging systems for food cold chain express based on life cycle assessment - Teng Meng; Yinpu Wang; Lin Fu; Yuelin Wang; Na Zhang; Zhao Wang; Qi Yang (Journal of Cleaner Production, 2023)

Cannabidiol protects the liver from α-Amanitin-induced apoptosis and oxidative stress through the regulation of Nrf2 - Haowei Wang; Genmeng Yang; Xiaoxing Zhang; Huijie Zhang; Yan Liu; Chan Wang; Lin Miao; Yi Li; Yizhen Huang; Hanxin Teng; Shangwen Wang; Hao Cheng; et al. (Food and Chemical Toxicology, 2023)

Influencing Factors and New Reference Intervals of Adult Thyroid Volume in Iodine-Sufficient Areas of China - Zheyu Lin; Cihang Lu; Di Teng; Ying Sun; Tingting Liu; Yongze Li; Zhongyan Shan; Weiping Teng (Biological Trace Element Research, 2023)
The diagnosis of goiter is based on the thyroid volume measured by ultrasound in which iodine plays an important role. The purpose of this study was to evaluate the factors that affect thyroid volume and update the reference range of thyroid volume to provide a new basis for the diagnosis and treatment of goiter. A study population from mainland China was evaluated in the Thyroid disorders, Iodine status and Diabetes Epidemiological (TIDE) study. Thyroid size was measured by ultrasound, and thyroid volume was calculated. A quantile regression model was used to analyze the influence of related factors on the thyroid volume at each percentile. The median urinary iodine concentration (UIC) was 185.54 μg/l. The quantile regression model suggested that body surface area (BSA) and thyroid-stimulating hormone (TSH) were positive and negative factors for thyroid volume, respectively ( p < 0.01). Excess iodine reduces the median and lower limits of thyroid volume. In iodine-sufficient areas, smoking is no longer a risk factor. The reference value range of thyroid volume stratified by sex was 3.92–19.06 ml for males and 3.1–16.17 ml for females. The maximum reference ranges for stratification by sex and BSA were 4.25–20.98 ml for men and 3.44–18.31 ml for women. The iodine nutrition level of the population in mainland China is sufficient. Iodine has the potential to alter the effect of certain factors on thyroid volume and effect is not regional. The new reference interval of adult thyroid volume based on sex and BSA has been updated, which can be used as a reliable reference for updating the diagnostic criteria of endemic goiter.

Leaf traits and temperature shape the elevational patterns of phyllosphere microbiome - Xing Wang; Zuoqiang Yuan; Arshad Ali; Teng Yang; Fei Lin; Zikun Mao; Ji Ye; Shuai Fang; Zhanqing Hao; XugaoWang; Yoann Le Bagousse‐Pinguet (Journal of Biogeography, 2023)
Aim The phyllosphere microbiome is central to plant health, distribution, and ecosystem function, yet, we lack a clear understanding of the drivers shaping their diversity in mountain ranges. Here, we examined how the endo‐ and epiphytic phyllosphere microbiomes of mountains simultaneously respond to climate and leaf functional traits. Location Temperate forests of Changbai Mountain Natural Reserve, China. Methods We collected the leaves of dominant tree species along seven elevations from 800 to 1950. We investigated changes in species richness and Shannon diversity of endo‐ and epiphytic phyllosphere fungal and bacterial communities (using next‐generation sequencing of ITS2 and 16S) along an 1150 m elevational gradient. We also examined the direct and indirect effects of climate (mean annual temperature; MAT) and 13 leaf morphological and chemical traits on the microbiome of the phyllosphere. Results Phyllosphere microbiome declined monotonically with increasing elevation, contrasting with the hump‐shaped biodiversity patterns that are commonly reported. We observed a steeper decline in epiphytic bacterial diversity than in endophytic bacteria, whereas conversely endophytic fungi diversity declined more dramatically with increasing elevation than epiphytic fungi. Host plant traits – those involved in resource uptake and leaf surface temperature – predominantly shaped the elevational patterns of endophytic phyllosphere microbiome, whereas MAT mostly increased the richness and Shannon diversity of epiphytic organisms. We also observed weak, but significant indirect effects suggesting that host plant traits are important biotic drivers mediating climate effects on endophytic phyllosphere microbiome. Also, no covariation between bacteria and fungi was observed (neither for endophytic nor for epiphytic organisms), supporting neutral associations between bacterial and fungal communities, irrespective of the elevation. Main Conclusions Both direct and mediating effects of plant traits should be considered to better understand the drivers shaping the richness and Shannon diversity of endo‐ and epiphytic phyllosphere microbiomes, and more generally the plant–microbe associations. Our study also offers a trait‐based attempt to disentangle the effects of biotic and abiotic filters in shaping endo‐ and epiphytic phyllosphere microbiome along an elevational gradient.

Optimizing aeration intensity to enhance self-flocculation in algal-bacterial symbiosis systems - Jiahui Huang; Sihan Cheng; Yuwei Zhang; Jiaheng Teng; Meijia Zhang; Hongjun Lin (Chemosphere, 2023)

Distribution and co-occurrence networks of the bacterial community in sediment cores from the subtropical Daya Bay, China - Peng Wu; Yong Liu; Chunhou Li; Qiushi Zheng; Yiguo Hong; Jiapeng Wu; Shannan Xu; Lin Lin; Yayuan Xiao; Teng Wang; Yu Liu (Marine Pollution Bulletin, 2023)

The iLABdb: a web-based integrated lactic acid bacteria database - Hao Jin; Teng Ma; Lin Chen; Lai-Yu Kwok; Keyu Quan; Yalin Li; Zeng Zhang; Tong Chen; Jiachao Zhang; Zhihong Sun; Heping Zhang (Science Bulletin, 2023)

Long-term PM2.5 concentration prediction based on improved empirical mode decomposition and deep neural network combined with noise reduction auto-encoder- A case study in Beijing - Mengfan Teng; Siwei Li; Jie Yang; Shuo Wang; Chunying Fan; Yu Ding; Jiaxin Dong; Hao Lin; Shansi Wang (Journal of Cleaner Production, 2023)

Relationships between starch molecular components and eating and cooking qualities of rice using single-segment substitution lines with different Wx loci - Lingshang Lin; Yuanjiang Wang; Xin Xu; Bin Teng; Cunxu Wei (Journal of Cereal Science, 2023)

Evaporative emission characteristics of VOCs from in-use light-duty gasoline vehicles - Teng Zi; Pengrui Wang; Baoxian Liu; Ying Zhou; Xiu'e Shen; Lin Zhang; Yang Lu; Qian Feng; Yanyan Yang; Jianlei Lang (Atmospheric Environment, 2023)

Design and verification of a wearable wireless 64-channel high-resolution EEG acquisition system with wi-fi transmission - Chin-Teng Lin; Yuhling Wang; Sheng-Fu Chen; Kuan-Chih Huang; Lun-De Liao (Medical & Biological Engineering & Computing, 2023)

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

Bifidobacterium spp. as functional foods: A review of current status, challenges, and strategies - Bao-Lin He; Yong Xiong; Teng-Gen Hu; Min-Hua Zong; Hong Wu (Critical Reviews in Food Science and Nutrition, 2023)

Phenotypic screening of novel probiotics with potential anti-neuroinflammation activity based on cell and zebrafish models - Bao-Lin He; Teng-Gen Hu; Hong Wu (Food Bioscience, 2023)

Novel thermodynamic mechanisms of co-conditioning with polymeric aluminum chloride and polyacrylamide for improved sludge dewatering: A paradigm shift in the field - Yansha Zeng; Zhe Wang; Zhenxiang Pan; Liguo Shen; Jiaheng Teng; Hongjun Lin; Jianzhen Zhang (Environmental Research, 2023)

Titanium oxide nanotubes intercalated two-dimensional MXene composite membrane with exceptional antifouling and self-cleaning properties for oil/water separation - Qianqian Zeng; Die Ling Zhao; Liguo Shen; Hongjun Lin; Ning Kong; Lei Han; Cheng Chen; Jiaheng Teng; Chuyang Tang; Tai-Shung Chung (Chemical Engineering Journal, 2023)

Spatial-temporal evaluation of PM2.5 concentration for health risk reduction strategy development in a basin with different weather patterns - Ho-Wen Chen; Chien-Yuan Chen; Teng-Wei Chang; Guan-Yu Lin (Atmospheric Pollution Research, 2023)

SERS-based rapid susceptibility testing of commonly administered antibiotics on clinically important bacteria species directly from blood culture of bacteremia patients - Yin-Yi Han; Jann-Tay Wang; Wei-Chih Cheng; Ko-Lun Chen; Yi Chi; Lee-Jene Teng; Juen-Kai Wang; Yuh-Lin Wang (World Journal of Microbiology and Biotechnology, 2023)
Bloodstream infections are a growing public health concern due to emerging pathogens and increasing antimicrobial resistance. Rapid antibiotic susceptibility testing (AST) is urgently needed for timely and optimized choice of antibiotics, but current methods require days to obtain results. Here, we present a general AST protocol based on surface-enhanced Raman scattering (SERS-AST) for bacteremia caused by eight clinically relevant Gram-positive and Gram-negative pathogens treated with seven commonly administered antibiotics. Our results show that the SERS-AST protocol achieves a high level of agreement (96% for Gram-positive and 97% for Gram-negative bacteria) with the widely deployed VITEK 2 diagnostic system. The protocol requires only five hours to complete per blood-culture sample, making it a rapid and effective alternative to conventional methods. Our findings provide a solid foundation for the SERS-AST protocol as a promising approach to optimize the choice of antibiotics for specific bacteremia patients. This novel protocol has the potential to improve patient outcomes and reduce the spread of antibiotic resistance.

Genome-wide DNA methylation landscape of four Chinese populations and epigenetic variation linked to Tibetan high-altitude adaptation - Zeshan Lin; Yan Lu; Guoliang Yu; Huajing Teng; Bao Wang; Yajun Yang; Qinglan Li; Zhongsheng Sun; Shuhua Xu; Wen Wang; Peng Tian (Science China Life Sciences, 2023)

Fabrication of durable self-cleaning photocatalytic coating with long-term effective natural light photocatalytic degradation performance - Jinghang Feng; Qingge Feng; Jingbo Xin; Qihua Liang; Xiang Li; Kao Chen; Jiayang Teng; Sinan Wang; Lin Feng; Junyi Liu (Chemosphere, 2023)

Superior performance of a membrane bioreactor through innovative in-situ aeration and structural optimization using computational fluid dynamics - Liguo Shen; Qihang Wu; Qunfeng Ye; Hongjun Lin; Jianzhen Zhang; Cheng Chen; Rong Yue; Jiaheng Teng; Huachang Hong; Bao-Qiang Liao (Water Research, 2023)

New mechanisms of biochar-assisted vermicomposting by recognizing different active di-(2-ethylhexyl) phthalate (DEHP) degraders across pedosphere, charosphere and intestinal sphere - Shuwen Luo; Zhen Zhen; Tingting Teng; Weilong Wu; Guiqiong Yang; Changhong Yang; Huijun Li; Fengcheng Huang; Ting Wei; Zhong Lin; Dayi Zhang (Journal of Hazardous Materials, 2023)

Analysis of energy, exergy and CO2 emissions in a fiberglass furnace with oxy-fuel combustion - Yuan Yao; Jun-yao He; Qi Chen; Teng Li; Bo Li; Xiao-lin Wei (Fuel, 2023)

PIAS1 impedes vascular endothelial injury and atherosclerotic plaque formation in diabetes by blocking the RUNX3/TSP-1 axis - Qingsong Jin; Tiantian Zhao; Liangyan Lin; Xiaoyan Yao; Yaqin Teng; Dongdong Zhang; Yongjun Jin; Meizi Yang (Human Cell, 2023)

Fog and rain water chemistry in a tea plantation of northern Taiwan - Yi-Tzu Wang; Neng-Huei Lin; Chung-Te Chang; Jr-Chuan Huang; Teng-Chiu Lin (Environmental Science and Pollution Research, 2023)

Melatonin alleviates cisplatin-induced mice spermatogenesis defects - Zhu Peng; Wang Zhi Xin; Zhang Yu Sheng; Teng Zi; Liu Ya Nan; Wang Ze Lin; Liu Fu Jun; Liu Xue Xia (Reproductive Toxicology, 2023)

Breaking the cost barrier: polydopamine@NixCo100-x nanotubes as efficient photocatalysts for organic pollutant degradation - Qianqian Zeng; Hongjun Lin; Yang Qu; Zhengyi Huang; Ning Kong; Lei Han; Cheng Chen; Bisheng Li; Jiaheng Teng; Yanchao Xu; Liguo Shen (Journal of Cleaner Production, 2023)

Phenolic compound profile and gastrointestinal action of Solanaceae fruits: Species-specific differences - Changan Zhu; Min Zhang; Shuwen Wang; Xinhao Gao; Teng Lin; Jingquan Yu; Jinhu Tian; Zhangjian Hu (Food Research International, 2023)

A novel flower-like nickel-metal-organic framework (Ni-MOF) membrane for efficient multi-component pollutants removal by gravity - Lei Han; Jing Ma; Hongjun Lin; Cheng Chen; Jiaheng Teng; Bisheng Li; Dieling Zhao; Yanchao Xu; Wei Yu; Liguo Shen (Chemical Engineering Journal, 2023)

Assessment of various conditions for the simultaneous determination of US EPA and EU priority PAHs in coffee samples and their PAHs consumption risk - Yu-Fang Huang; Po-Lin Liao; Yi-Jun Lin; Shih-Han Huang; Yi-Hsieng Samuel Wu; Chia-Fang Teng; Deng-Jye Yang (Food Research International, 2023)

Cadmium exposure caused cardiotoxicity in common carps (Cyprinus carpio L.): miR-9-5p, oxidative stress, energetic impairment, mitochondrial division/fusion imbalance, inflammation, and autophagy - Yuhao Liu; Xu Lin; Zhiyu Hao; Meijin Yu; You Tang; Xiaohua Teng; Wei Sun; Lu Kang (Fish & Shellfish Immunology, 2023)

Development of a high-fidelity failure prediction system for reinforced concrete bridge columns using generative adversarial networks - Ting-Yan Wu; Rih-Teng Wu; Ping-Hsiung Wang; Tzu-Kang Lin; Kuo-Chun Chang (Engineering Structures, 2023)

Atmospheric benzo[a]pyrene in the Yangtze River Delta, China: pollution level and lung cancer risk in 2016 and future predictions - Baojie Li; Yingzhen Lin; Teng Wang; Wanyanhan Jiang; Xiaorui Wang (Environmental Geochemistry and Health, 2023)

Multifunctional nanocomposites induce mitochondrial dysfunction and glucose deprivation to boost immunogenic ferroptosis for cancer therapy - Cong Huang; Xiaosheng Lin; Teng Lin; Wenqiang Lin; Zhenqi Gong; Qing Zheng; Baizhi Li; Huaiming Wang (Chemical Engineering Journal, 2023)

Facile solvent-free radical polymerization to prepare itaconate-functionalized hydrochar for efficient sorption of methylene blue and Pb(II) - Hua-Jing Teng; Tao Xia; Cheng Li; Jian-Zhong Guo; Lin Chen; Chunzheng Wu; Bing Li (Bioresource Technology, 2023)

Protective Effect of Ergothioneine Against Stroke in Rodent Models - Wei-Yi Ong; Mei-Han Kao; Wai-Mui Cheung; Damien Meng-Kiat Leow; Irwin Kee-Mun Cheah; Teng-Nan Lin (NeuroMolecular Medicine, 2023)

Warming Increased Metabolite Composition and Pathways in Root Exudates of Chinese Fir Saplings in Subtropical China - Decheng Xiong; Jinxue Huang; Teng-Chiu Lin; Xiaofei Liu; Chao Xu; Shidong Chen; Zhijie Yang; Guangshui Chen; Yusheng Yang (Journal of Soil Science and Plant Nutrition, 2023)

Changes in soil microbial biomass, diversity, and activity with crop rotation in cropping systems: A global synthesis - Qing Liu; Yingxing Zhao; Teng Li; Lin Chen; Yuanquan Chen; Peng Sui (Applied Soil Ecology, 2023)

Plant and fungal species interactions differ between aboveground and belowground habitats in mountain forests of eastern China - Teng Yang; Leho Tedersoo; Pamela S. Soltis; Douglas E. Soltis; Miao Sun; Yuying Ma; Yingying Ni; Xu Liu; Xiao Fu; Yu Shi; Han-Yang Lin; Yun-Peng Zhao; et al. (Science China Life Sciences, 2023)

Characteristics and mechanisms of the intraseasonal variability of sea surface salinity in the southeastern Arabian Sea during 2015–2020 - Hui Teng; Yun Qiu; Xinyu Lin; Xiwu Zhou (Acta Oceanologica Sinica, 2023)

Understanding the 0 + + and 2 + + charmonium(-like) states near 3.9 GeV - Teng Ji; Xiang-Kun Dong; Miguel Albaladejo; Meng-Lin Du; Feng-Kun Guo; Juan Nieves; Bing-Song Zou (Science Bulletin, 2023)

ROS filter coating scaffold protects 3D mesenchymal stem cell spheroids for dual-phase treatment of spinal cord injury - Jian Cao; Jiahe Wu; Jiafu Mu; Lingmin Lin; Xunqi Zhang; Tianchen Huang; Teng Ma; Manning Zhu; Xiaoyang Dai; Xuhua Wang; Shiqing Feng; Jian-Qing Gao (Chemical Engineering Journal, 2023)

Biomass production and astaxanthin accumulation of Haematococcus pluvialis in large-scale outdoor culture based on year-round survey: Influencing factors and physiological response - Zhuoran Teng; Lingling Zheng; Zihan Yang; Lurong Li; Qi Zhang; Lin Li; Wei Chen; Gaohong Wang; Lirong Song (Algal Research, 2023)

China Brain Project: from bench to bedside - Xiaoxing Liu; Teng Gao; Tangsheng Lu; Yanping Bao; Gunter Schumann; Lin Lu (Science Bulletin, 2023)

Infant food production environments: A potential reservoir for vancomycin-resistant enterococci non-nosocomial infections - Zining Wang; Sihao Liao; Guanwen Huang; Mengyao Feng; Rui Yin; Lin Teng; Chenghao Jia; Yicheng Yao; Min Yue; Yan Li (International Journal of Food Microbiology, 2023)

Structure and hepatoprotective activity of Usp10/NF-κB/Nrf2 pathway-related Morchella esculenta polysaccharide - Shanshan Teng; Yongfeng Zhang; Xinghui Jin; Yanfeng Zhu; Lanzhou Li; Xiaowei Huang; Di Wang; Zhe Lin (Carbohydrate Polymers, 2023)

Extreme wind speed prediction in mountainous area with mixed wind climates - Teng Ma; Wei Cui; Lin Zhao; Ding Yejun; Fang Genshen; Yaojun Ge (Stochastic Environmental Research and Risk Assessment, 2023)

Ambient nitrogen dioxide and cardiovascular diseases in rural regions: a time-series analyses using data from the new rural cooperative medical scheme in Fuyang, East China - Teng-Fei Dong; Zhen-Qiu Zha; Liang Sun; Ling-Li Liu; Xing-Yang Li; Yuan Wang; Xiang-Long Meng; Huai-Biao Li; Hong-Li Wang; Huan-Huan Nie; Lin-Sheng Yang (Environmental Science and Pollution Research, 2023)

3D printing titanium dioxide-acrylonitrile-butadiene-styrene (TiO2-ABS) composite membrane for efficient oil/water separation - Lei Han; Liguo Shen; Hongjun Lin; Zhengyi Huang; Yanchao Xu; Renjie Li; Bisheng Li; Cheng Chen; Wei Yu; Jiaheng Teng (Chemosphere, 2023)

The extract from aerial part of Scutellaria baicalensis regulates gut microbiota in rabbit fish: Replacement of antibiotic fighting against pathogenic bacteria - Yi-Teng Xia; Edwin Hok-Chi Cheng; Huai-You Wang; Lynn Hoi-Lam Zhang; Sheng-Ying Lin; Tina Ting-Xia Dong; Ran Duan; Qi-Wei Qin; Wen-Xiong Wang; Karl Wah-Keung Tsim (Aquaculture, 2023)

RETRACTED: Boronic acid-modified bacterial cellulose microspheres as packing materials for enveloped virus removal - Zhiyang Lin; Linhan Li; Kaige Song; Bin Yang; Guoqing Zhou; Gengrong Zhang; Jiang Teng; Erlong Wang; Xiaoqiang Liu; Fei Ling; Gaoxue Wang; Tianqiang Liu (Science of The Total Environment, 2023)

InSAR-based investigation on spatiotemporal characteristics of river sediment behavior - Shih-Yuan Lin; Shih-Teng Chang; Ching-Fang Lee (Journal of Hydrology, 2023)

Marker-assisted breeding of rice lines special for rice noodle-making by pyramiding the Wxg2 and ALKGC genes - Bin Teng; Fengshun Song; Quan Gan; Cuixiang Lin; Dahu Ni (Euphytica, 2023)

Application of convolutional neural networks based on Bayesian optimization to landslide susceptibility mapping of transmission tower foundation - Mansheng Lin; Shuai Teng; Gongfa Chen; Bo Hu (Bulletin of Engineering Geology and the Environment, 2023)

Labile and refractory fractions of sedimentary organic carbon off the Changjiang Estuary and its implications for sedimentary oxygen consumption - Yu Cao; Hong Huang; Xu Zhao; Jun Li; Teng Wang; Jun Lin; Zhuo-Yi Zhu (Frontiers in Marine Science, 2023)
Estuarine and coastal area is dynamic zone for both marine carbon and oxygen cycles. There is limited evaluation of the labile and refractory fraction of sedimentary organic carbon and further a lack of attention to the corresponding potential in dissolved oxygen utilization. In this study, we collected sediment samples from the Changjiang estuary and adjacent coastal areas in the East China Sea in June 2019 to reveal the distribution, main controlling factor, and implications of four operational fractions of sediment organic carbon that range from labile to refraction. In the laboratory, we processed and defined the four operational fractions of sedimentary organic carbon, includes 1) pure water extractable carbon (WEC), 2) salt (K2SO4 solution) extractable carbon (SEC), 3) Microbial biomass carbon (MBC; chloroform extractable carbon), and 4) refractory organic carbon (ROC; the acid-processed fraction). We revealed that off the Changjiang Estuary, the bulk sedimentary organic carbon (SOC), WEC, SEC, MBC, and ROC were 9.43 ± 3.07 g/kg, 0.12 ± 0.10 g/kg, 0.16 ± 0.07 g/kg, 1.58 ± 0.45 g/kg, and 4.38 ± 1.95 g/kg, respectively. Sediment grain size played a vital role in constraining the LOC fractions, and samples from aquaculture areas showed extra-higher levels of LOC when compared to samples from the non-aquaculture area. The LOC and MBC fraction showed clear negative relation with dissolved oxygen (DO) in the near bottom waters under high DO background (DO > 5.5 mg/L), whereas in a low DO background (DO < 3-4 mg/L) no clear relation can be found. Based on our observed LOC content and DO concentration in the near bottom waters, the depth of hypoxia in the near bottom waters, which would be caused by a total decomposition of 4 mm of LOC in the top sediment, ranged between 0.3 m to 4.7 m with an average depth of 2 m. This value (2 m) means that sedimentary oxygen consumption would contribute 10% in the occurrence of hypoxia, with the rest contributing from water column respiration. Overall, we used the LOC fraction of sedimentary organic carbon to address the dissolved oxygen consumption in the near bottom waters and further study is needed to evaluate this approach.

Mitigation of protein fouling by magnesium ions and the related mechanisms in ultrafiltration process - Hui Zou; Jiahui Huang; Meijia Zhang; Hongjun Lin; Jiaheng Teng; Zhengyi Huang (Chemosphere, 2023)

Within-species plant phylogeny drives ectomycorrhizal fungal community composition in tree roots along a timberline - Teng Yang; Luyao Song; Han-Yang Lin; Ke Dong; Xiao Fu; Gui-Feng Gao; Jonathan M. Adams; Haiyan Chu (Soil Biology and Biochemistry, 2023)

Target anisotropic scattering deduction model using multi-aspect SAR data - Xiaoyang Yue; Fei Teng; Yun Lin; Wen Hong (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Meniscus inspired flexible superhydrophobic coating with remarkable erosion resistance for pipeline gas transmission - Xuerui Zang; Xuewen Cao; Weiwei Zheng; Tianxue Zhu; Yonggang Lei; Jianying Huang; Zhong Chen; Lin Teng; Jiang Bian; Yuekun Lai (Chemical Engineering Journal, 2023)

Genetic lineage tracing identifies cardiac mesenchymal-to-adipose transition in an arrhythmogenic cardiomyopathy model - Xinyan Huang; Lei Yan; Jufeng Meng; Nanbo Liu; Shuoji Zhu; Zhen Jiang; Shan Kou; Teng Feng; Chao-Po Lin; Bin Zhou; Juan Tang; Ping Zhu; et al. (Science China Life Sciences, 2023)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Orientin downregulating oxidative stress-mediated endoplasmic reticulum stress and mitochondrial dysfunction through AMPK/SIRT1 pathway in rat nucleus pulposus cells in vitro and attenuated intervertebral disc degeneration in vivo - Zhao Zhang; Jingtao Wu; Cheng Teng; Jinquan Wang; Jiapei Yu; Chen Jin; Libo Wang; Long Wu; Zhen Lin; Ziping Yu; Zhongke Lin (Apoptosis, 2022)

Two new phenylpropenoid glycosides from the roots of Illicium dunnianum - Yi-lin Wang; Han Li; Ling Song; Yun-hang Gao; Teng-fei Chen (Natural Product Research, 2022)

Prenylaromadendrane-type diterpenoids from the gum resin of Boswellia sacra flueck and their cytotoxic effects - Jia-Jia Wang; Xin-Yue Suo; Hao-Ran Sun; Xue Wang; Ming-Bao Lin; Jin-Hua Wang; Jian-Dong Jiang; Teng-Fei Ji (Natural Product Research, 2022)

Insights into the interaction between cadmium/tetracycline and nano-TiO2 on a zeolite surface - Teng Wang; Zhaofu Meng; Lin Liu; Wenbin Li (Environmental Science and Pollution Research, 2022)

Measuring the phase response of a seismometer using superimposed sine signals - Zhan Lin; Yuntian Teng; Bing Xue; Xinxin Ma (Journal of Seismology, 2022)

Analysis of water–rock interaction in Middle-Lower Ordovician strike-slip fault in T-SH Oilfield, Tarim Basin, NW China - Teng Zhao; Rui Zhao; Qiangfu Kong; Chongyang Xiao; Huixi Lin (Carbonates and Evaporites, 2022)

Geomechanics model test and numerical simulation of 2G-NPR bolt support effect in an active fault tunnel - Shu-lin Ren; Man-chao He; Wei-jun Lin; Teng-wu Zhang; Zhi-gang Tao (Journal of Mountain Science, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Differences of Macroalgal Consumption by Eight Herbivorous Coral Reef Fishes From the Xisha Islands, China - Peng Wu; Teng Wang; Yong Liu; Chunhou Li; Yayuan Xiao; Shannan Xu; Tingting Han; Lin Lin; Qiumei Quan (Frontiers in Marine Science, 2022)
Herbivorous fishes play an important role in preventing the overabundance of macroalgae on coral reefs. Understanding the feeding selectivity and consumption of macroalgae by herbivorous fishes can be challenging in studies of their ecological role in the preservation and recovery of coral reefs. Coral reef decline, macroalgal overgrowth and overfishing are clearly visible in the Xisha Islands, China. However, there are seldom studies on the feeding behaviors of herbivorous fishes in this area. We used microscopy, 18S rRNA high-throughput sequencing, and stable isotope analyses to comprehensively examine the diet of eight herbivorous reef fish species common in the Xisha Islands, including one parrotfish, two chub, two unicorn fish, and three rabbitfish. Based on microscopic examination, Siganus argenteus fed on the highest number of macroalgae species (five species), followed by Naso unicornis (four species). Kyphosus cinerascens , K. vaigiensis , N. unicornis and S. punctatissimus fed on the entire macroalgal thallus, indicating their greater ecological importance compared with species that only consume algal fronds. According to the 18S rRNA high-throughput sequencing of fish intestinal contents, cluster analysis revealed that consumed macroalgae composition from the eight fishes always grouped together based on the fish species, but with low similarity. K. vaigiensis removed the highest diversity of macroalgae species as well as the greatest quantity of macroalgae. Calotomus carolinus can consume the red alga Pneophyllum conicum , which is widely distributed on Indo-Pacific coral reefs and can overgrow and kill live corals. N. unicornis was found to occupy the lowest trophic position based on stable isotope analysis. Multi-technique analyses revealed that K. vaigiensis , N. unicornis and S. argenteus showed a high consumption potential of macroalgae, suggesting that they are the key browsers that should receive priority protection in the Xisha Islands. A diverse herbivorous fish fauna is also very important in the Xisha coral reefs. These results not only demonstrated the various functions of different herbivorous fish species in macroalgal removal, but also provided insights into the management of herbivorous fishes on the coral reefs of the South China Sea.

miR-183-5p promotes proliferation, invasion, and glycolysis of thyroid carcinoma cells by targeting FOXO1 - Chun Han; Kangnan Mo; Lin Jiang; Kejing Wang; Lisong Teng (Molecular and Cellular Biochemistry, 2022)

Association of genetic polymorphisms of VAX1, MAFB, and NTN1 with nonsyndromic cleft lip with or without cleft palate in Chinese population - Li Peng; Zhenmin Niu; Jiapei Chen; Teng Wan; Dandan Wu; Yusheng Yang; Guomin Wang; Lin Yang; Wei Huang; Zhenqi Chen (Molecular Genetics and Genomics, 2022)

Disturbance frequency, intensity and forest structure modulate cyclone‐induced changes in mangrove forest canopy cover - Jonathan Peereman; J. Aaron Hogan; Teng‐Chiu Lin (Global Ecology and Biogeography, 2022)
Aim Tropical cyclones are large‐scale disturbances that can shape the structure and dynamics of mangrove forests. Although tropical cyclone activity overlaps extensively with the latitudinal distribution of mangrove forests, the relationships between cyclone intensity and frequency and mangrove forest canopy damage and recovery are not understood at the global scale. Using remote sensing data, we examined how mangrove forest structure, climate and cyclone characteristics influence canopy cover loss and recovery dynamics. Location Global tropics. Time period 2000–2020. Major taxa studied Mangrove trees. Methods Using two satellite‐derived vegetation indices (the enhanced vegetation index and the normalized difference infrared index) from 86 cyclones affecting 56 mangrove sites across the globe, we quantified mangrove canopy loss in relationship to cyclones. Using linear regression and variance decomposition, we identified and ranked significant predictors of cyclone‐induced canopy loss and recovery. Results Three‐quarters of the studied cyclone disturbances resulted in canopy damage. Stands exposed to high wind speeds and those close to the cyclone paths were more severely damaged, whereas lower damage magnitudes were found in sites with greater past cyclone frequency. Canopy damage was greater in tall mangrove stands but decreased with higher aboveground biomass. The distance from the cyclone path and maximum wind speed were the most important factors, representing > 50% of the explained variation in cyclone damage. There was considerable variation in canopy damage among cyclones, but rates of recovery were similar across all mangrove sites, with the main predictor of recovery time being the degree of canopy loss. Main conclusions Our results suggest that the resistance of mangrove canopy cover to cyclone disturbance is variably tuned to the cyclone regime and vegetation characteristics, but resilience is inherent to the magnitude of canopy damage because the rate of forest canopy recovery appears to be consistent globally.

Evolution characteristics of mining fissures in overlying strata of stope after converting from open-pit to underground - Xiaoshuang Li; Qihang Li; Yunjin Hu; Lin Teng; Shun Yang (Arabian Journal of Geosciences, 2021)

Characterization and identification of SFDC ‐1, a novel AmpC ‐type β‐lactamase in Serratia fonticola - Xu Dong; Peiyao Zhang; Kexin Zhou; Jialei Liang; Qiaoling Li; Xueya Zhang; Danying Zhou; Wei Lu; Zhewei Sun; Hongmao Liu; Junwan Lu; Xi Lin; et al. (Environmental Microbiology, 2021)
Summary The clinical and environmental infections caused by AmpC β‐lactamases have been increasingly reported recently. In this study, we characterize the novel chromosome‐encoded AmpC β‐lactamase SFDC‐1 identified in Serratia fonticola strain R28, which was isolated from a rabbit raised on a farm in southern China. SFDC‐1 shared the highest amino acid identity of 79.6% with the functionally characterized AmpC β‐lactamase gene bla YRC‐1 , although it had highly homologous functionally uncharacterized relatives in the same species from different sources, including some of the clinical significance. The cloned bla SFDC‐1 exhibited resistance to a broad spectrum of β‐lactam antibiotics, including most cephalosporins with the highest resistance to ampicillin, cefazolin and ceftazidime, with increased MIC levels ≥128‐fold compared with the control strains. The purified SFDC‐1 showed catalytic activities against β‐lactams with the highest catalytic activity to cefazolin. The genetic context of bla SFDC‐1 and its relatives was conserved in the chromosome, and no mobile genetic elements were found surrounding them.

Maternal Subclinical Hypothyroidism in Rats Impairs Spatial Learning and Memory in Offspring by Disrupting Balance of the TrkA/p75NTR Signal Pathway - Fan Zhang; Xinyue Lin; Aihua Liu; Jian Chen; Zhongyan Shan; Weiping Teng; Xiaohui Yu (Molecular Neurobiology, 2021)
Maternal subclinical hypothyroidism (SCH) during pregnancy can adversely affect the neurodevelopment of the offspring. The balance of nerve growth factor (NGF)-related tropomyosin receptor kinase A/p75 neurotrophin receptor (TrkA/p75 NTR ) signaling in the hippocampus is important in brain development, and whether it affects cognitive function in maternal SCH’s offspring is not clear. In this study, we found that compared with the control (CON) group, expression of proliferation-related proteins [NGF, p-TrkA, phospho-extracellular signal-regulated kinase 1/2 (p-ERK1/2) and phospho-cAMP response element-binding protein (p-CREB)] decreased in the hippocampus of the offspring in the SCH group, overt hypothyroidism (OHT) group, and the group with levothyroxine (L-T 4 ) treatment for SCH from gestational day 17 (E17). In contrast, expression of apoptosis-related proteins [pro-NGF, p75 NTR , phospho-C-Jun N-terminal kinase (p-JNK), p53, Bax and cleaved caspase-3] was increased. The two groups with treatment with L-T 4 for SCH from E10 and E13, respectively, showed no significant difference compared with the CON group. L-T 4 treatment enhanced relative expression of NGF by increasing NGF/proNGF ratio in offspring from maternal SCH rats. In conclusion, L-T 4 treatment for SCH from early pregnancy dramatically ameliorated cognitive impairment via TrkA/p75 NTR signaling, which involved activation of the neuronal proliferation and inhibition of neuronal apoptosis in SCH rats’ offspring.

Present in-situ stress distribution characteristics of strike-slip in SH Oilfield, Tarim Basin - Teng Zhao; Wenge Hu; Rui Zhao; Min Yang; Qiang Wang; Huixi Lin; Zhixing Ru; Dian Bao; Fei Cao (Arabian Journal of Geosciences, 2021)

Clinacanthus nutans Mitigates Neuronal Death and Reduces Ischemic Brain Injury: Role of NF-κB-driven IL-1β Transcription - Mei-Han Kao; Jui-Sheng Wu; Wai-Mui Cheung; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Deron R. Herr; Teng-Nan Lin (NeuroMolecular Medicine, 2021)

Description of the reservoir along strike-slip fault zones in China T-Sh oilfield, Tarim Basin - Rui Zhao; Shang Deng; Lu Yun; Huixi Lin; Teng Zhao; Chen Yu; Qiangfu Kong; Qiang Wang; Huili Li (Carbonates and Evaporites, 2021)

The bacterial composition associated with Atriolum robustum, a common ascidian from Xisha coral reef, China - Yong Liu; Peng Wu; Chunhou Li; Yayuan Xiao; Teng Wang; Lin Lin (Symbiosis, 2021)

Identification and expression analysis of caffeoyl-coenzyme A O-methyltransferase family genes related to lignin biosynthesis in tea plant (Camellia sinensis) - Shi-Jia Lin; Ya-Zhuo Yang; Rui-Min Teng; Hao Liu; Hui Li; Jing Zhuang (Protoplasma, 2021)

Effects of shading on lignin biosynthesis in the leaf of tea plant (Camellia sinensis (L.) O. Kuntze) - Rui-Min Teng; Yong-Xin Wang; Hui Li; Shi-Jia Lin; Hao Liu; Jing Zhuang (Molecular Genetics and Genomics, 2021)

Transcriptome analysis of strawberry fruit in response to exogenous arginine - Jinhua Lv; Qianqian Pang; Xueqin Chen; Teng Li; Jinggui Fang; Shaoyan Lin; Haifeng Jia (Planta, 2020)

Analysis of HBsAg mutations in the 25 years after the implementation of the hepatitis B vaccination plan in China - Huiming Ye; Jing Teng; Zhiyuan Lin; Ye Wang; Xiaochun Fu (Virus Genes, 2020)

Nitrogen and phosphorus co-starvation inhibits anthocyanin synthesis in the callus of grape berry skin - Hui-Zhen Zheng; Huan Wei; Shui-Huan Guo; Xin Yang; Ming-Xin Feng; Xu-Qiao Jin; Yu-Lin Fang; Zhen-Wen Zhang; Teng-Fei Xu; Jiang-Fei Meng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Correction to: Effects of nitrogen addition on DOM-induced soil priming effects in a subtropical plantation forest and a natural forest - Yuexin Fan; Xiaojian Zhong; Teng-Chiu Lin; Maokui Lyu; Minhuang Wang; Weifang Hu; Zhijie Yang; Guangshui Chen; Jianfen Guo; Yusheng Yang (Biology and Fertility of Soils, 2020)

Effects of nitrogen addition on DOM-induced soil priming effects in a subtropical plantation forest and a natural forest - Yuexin Fan; Xiaojian Zhong; Teng-Chiu Lin; Maokui Lyu; Minhuang Wang; Weifang Hu; Zhijie Yang; Guangshui Chen; Jianfen Guo; Yusheng Yang (Biology and Fertility of Soils, 2020)

Root litter inputs exert greater influence over soil C than does aboveground litter in a subtropical natural forest - Xiaofei Liu; Teng-Chiu Lin; Matthew A. Vadeboncoeur; Zhijie Yang; Shidong Chen; Decheng Xiong; Chao Xu; Yiqing Li; Yusheng Yang (Plant and Soil, 2019)

An integrated strategy to identify genes responsible for sesquiterpene biosynthesis in turmeric - Jingru Sun; Guanghong Cui; Xiaohui Ma; Zhilai Zhan; Ying Ma; Zhongqiu Teng; Wei Gao; Yanan Wang; Tong Chen; Changjiangsheng Lai; Yujun Zhao; Jinfu Tang; et al. (Plant Molecular Biology, 2019)

X-linked hyper-IgM syndrome complicated with interstitial pneumonia and liver injury: a new mutation locus in the CD40LG gene - Tian-Jiao Wang; Li-Fang Wu; Junguo Chen; Wen Zhu; Hua Wang; Xiao-Lin Liu; Yi-Qun Teng (Immunologic Research, 2019)

The complete chloroplast genome of Taiwania cryptomerioides (Cupressales: Cupressaceae), an endangered relict conifer species endemic to East Asia - Ling-Li Wang; Yong-Liang Shi; Qi-Lin Zhang; Yan-Ru Guo; Hong-Mei Teng (Conservation Genetics Resources, 2019)

Effect of a humic acid colloid on the sorption behaviour of Sr onto soil in a candidate high-level radioactive waste geological disposal site - Rui Zuo; Minhua Chen; Yuanhui Lin; Jie Yang; Shuhe Jin; Weifeng Yue; Jinsheng Wang; Yanguo Teng (Environmental Science and Pollution Research, 2019)

Effect of pH on Pollutants Removal of Ship Sewage Treatment in an Innovative Aerobic-Anaerobic Micro-Sludge MBR System - Yuhang Cai; Teng Ben; Asad A. Zaidi; Yue Shi; Kun Zhang; Aqiang Lin; Chen Liu (Water, Air, & Soil Pollution, 2019)

Characteristics of Old-Growth and Secondary Forests in Relation to Age and Typhoon Disturbance - Shin-Yu Lin; Pei-Jen Lee Shaner; Teng-Chiu Lin (Ecosystems, 2018)

Characterization of 108 novel expressed sequence tag-derived single-nucleotide polymorphism markers in the blood clam Tegillarca granosa using a transcriptome database - Shuangshuang Teng; Xingguan Lin; Jun Fang; Xueliang Chai; Guoqiang Xiao (Journal of Genetics, 2018)

Sensitivity of Cochliobolus heterostrophus to three demethylation inhibitor fungicides, propiconazole, diniconazole and prochloraz, and their efficacy against southern corn leaf blight in Fujian Province, China - Yuli Dai; Lin Gan; Hongchun Ruan; Niuniu Shi; Yixin Du; Lei Liao; Zhixia Wei; Zhenyong Teng; Furu Chen; Xiujuan Yang (European Journal of Plant Pathology, 2018)

Opioid Exposure is Associated with Aberrant DNA Methylation of OPRM1 Promoter Region in a Chinese Han Population - Jiawei Xu; Teng Wang; Zhiyang Su; Xinyao Zhou; Yuqian Xiang; Lin He; Candong Li; Zhaoyang Yang; Xinzhi Zhao (Biochemical Genetics, 2018)

Clinacanthus nutans Mitigates Neuronal Apoptosis and Ischemic Brain Damage Through Augmenting the C/EBPβ-Driven PPAR-γ Transcription - Jui-Sheng Wu; Mei-Han Kao; Hsin-Da Tsai; Wai-Mui Cheung; Jin-Jer Chen; Wei-Yi Ong; Grace Y. Sun; Teng-Nan Lin (Molecular Neurobiology, 2018)

Recombinant rabies virus expressing interleukin-6 enhances the immune response in mouse brain - Jun Luo; Boyue Zhang; Yuting Wu; Qin Tian; Meijun Mo; Teng Long; Mingzhu Mei; Ruqi Fan; Ziyu Lyu; He Jiang; Fan Wu; Yingyi Lin; et al. (Archives of Virology, 2018)

Necroptosis may be a novel mechanism for cardiomyocyte death in acute myocarditis - Fei Zhou; Xuejun Jiang; Lin Teng; Jun Yang; Jiawang Ding; Chao He (Molecular and Cellular Biochemistry, 2018)

Comparative growth increments of gladius surface and cross-sections to estimate Sthenoteuthis oualaniensis age - Xue Feng Wang; Bi Lin Liu; Jian Hua Li; Rui Jiang; Jing Yuan Lin; Teng Li (Marine Biology, 2018)

Characteristics of rock fragments in different forest stony soil and its relationship with macropore characteristics in mountain area, northern China - Chen Meng; Jian-zhi Niu; Zheng-cong Yin; Zi-teng Luo; Xing-na Lin; Jing-wei Jia (Journal of Mountain Science, 2018)

Temporal changes in soil C‐N‐P stoichiometry over the past 60 years across subtropical China - Zaipeng Yu; Minhuang Wang; Zhiqun Huang; Teng‐Chiu Lin; Matthew A. Vadeboncoeur; Eric B. Searle; Han Y. H. Chen (Global Change Biology, 2018)
Controlled experiments have shown that global changes decouple the biogeochemical cycles of carbon (C), nitrogen (N), and phosphorus (P), resulting in shifting stoichiometry that lies at the core of ecosystem functioning. However, the response of soil stoichiometry to global changes in natural ecosystems with different soil depths, vegetation types, and climate gradients remains poorly understood. Based on 2,736 observations along soil profiles of 0–150 cm depth from 1955 to 2016, we evaluated the temporal changes in soil C‐N‐P stoichiometry across subtropical China, where soils are P‐impoverished, with diverse vegetation, soil, and parent material types and a wide range of climate gradients. We found a significant overall increase in soil total C concentration and a decrease in soil total P concentration, resulting in increasing soil C:P and N:P ratios during the past 60 years across all soil depths. Although average soil N concentration did not change, soil C:N increased in topsoil while decreasing in deeper soil. The temporal trends in soil C‐N‐P stoichiometry differed among vegetation, soil, parent material types, and spatial climate variations, with significantly increased C:P and N:P ratios for evergreen broadleaf forest and highly weathered Ultisols, and more pronounced temporal changes in soil C:N, N:P, and C:P ratios at low elevations. Our sensitivity analysis suggests that the temporal changes in soil stoichiometry resulted from elevated N deposition, rising atmospheric CO 2 concentration and regional warming. Our findings revealed that the responses of soil C‐N‐P and stoichiometry to long‐term global changes have occurred across the whole soil depth in subtropical China and the magnitudes of the changes in soil stoichiometry are dependent on vegetation types, soil types, and spatial climate variations.

Diversity and evolution analysis of glycoprotein GP85 from avian leukosis virus subgroup J isolates from chickens of different genetic backgrounds during 1989-2016: Coexistence of five extremely different clusters - Peikun Wang; Lulu Lin; Haijuan Li; Yongli Yang; Teng Huang; Ping Wei (Archives of Virology, 2018)

Gender-Related Hippocampal Proteomics Study from Young Rats After Chronic Unpredicted Mild Stress Exposure - Lin-Na Ning; Teng Zhang; Jiang Chu; Na Qu; Li Lin; Ying-Yan Fang; Yan Shi; Peng Zeng; Er-Li Cai; Xiao-Ming Wang; Qun Wang; You-Ming Lu; et al. (Molecular Neurobiology, 2018)

Identification and expression analysis of the Eucommia ulmoides farnesyl diphosphate synthase gene family to reveal the key gene involved in rubber biosynthesis - Lin Wang; Teng Jing; Tiezhu Li; Hongyan Du; Ta-na Wuyun (Acta Physiologiae Plantarum, 2018)

Full-length genome sequence analysis of four subgroup J avian leukosis virus strains isolated from chickens with clinical hemangioma - Lulu Lin; Peikun Wang; Yongli Yang; Haijuan Li; Teng Huang; Ping Wei (Virus Genes, 2017)

Acclimation of bloom‐forming and perennial seaweeds to elevated p CO 2 conserved across levels of environmental complexity - Dong Xu; Charlotte‐Elisa Schaum; Fan Lin; Ke Sun; James R. Munroe; Xiao W. Zhang; Xiao Fan; Lin H. Teng; Yi T. Wang; Zhi M. Zhuang; Naihao Ye (Global Change Biology, 2017)
Macroalgae contribute approximately 15% of the primary productivity in coastal marine ecosystems, fix up to 27.4 Tg of carbon per year, and provide important structural components for life in coastal waters. Despite this ecological and commercial importance, direct measurements and comparisons of the short‐term responses to elevated p CO 2 in seaweeds with different life‐history strategies are scarce. Here, we cultured several seaweed species (bloom forming/nonbloom forming/perennial/annual) in the laboratory, in tanks in an indoor mesocosm facility, and in coastal mesocosms under p CO 2 levels ranging from 400 to 2,000 μatm. We find that, across all scales of the experimental setup, ephemeral species of the genus Ulva increase their photosynthesis and growth rates in response to elevated p CO 2 the most, whereas longer‐lived perennial species show a smaller increase or a decrease. These differences in short‐term growth and photosynthesis rates are likely to give bloom‐forming green seaweeds a competitive advantage in mixed communities, and our results thus suggest that coastal seaweed assemblages in eutrophic waters may undergo an initial shift toward communities dominated by bloom‐forming, short‐lived seaweeds.

Increased litter in subtropical forests boosts soil respiration in natural forests but not plantations of Castanopsis carlesii - Xiaofei Liu; Teng-Chiu Lin; Zhijie Yang; Matthew A. Vadeboncoeur; Chengfang Lin; Decheng Xiong; Weisheng Lin; Guangshui Chen; Jinsheng Xie; Yiqing Li; Yusheng Yang (Plant and Soil, 2017)

Effects of HLA-DRB1/DQB1 Genetic Variants on Neuroimaging in Healthy, Mild Cognitive Impairment, and Alzheimer’s Disease Cohorts - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Jinyuan Liu; Yu Wan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Genetic Association of HLA Gene Variants with MRI Brain Structure in Alzheimer’s Disease - Zi-Xuan Wang; Yu Wan; Lin Tan; Jinyuan Liu; Hui-Fu Wang; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

HLA-A2 Alleles Mediate Alzheimer’s Disease by Altering Hippocampal Volume - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

PGRN Is Associated with Late-Onset Alzheimer’s Disease: a Case–Control Replication Study and Meta-analysis - Hui-Min Xu; Lin Tan; Yu Wan; Meng-Shan Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Impacts of CD33 Genetic Variations on the Atrophy Rates of Hippocampus and Parahippocampal Gyrus in Normal Aging and Mild Cognitive Impairment - Wen-Ying Wang; Ying Liu; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

A Missense Variant in TREML2 Reduces Risk of Alzheimer’s Disease in a Han Chinese Population - Teng Jiang; Yu Wan; Jun-Shan Zhou; Meng-Shan Tan; Qing Huang; Xi-Chen Zhu; Huan Lu; Hui-Fu Wang; Qi Chen; Lin Tan; Ying-Dong Zhang; Lan Tan; et al. (Molecular Neurobiology, 2017)

Effect of CR1 Genetic Variants on Cerebrospinal Fluid and Neuroimaging Biomarkers in Healthy, Mild Cognitive Impairment and Alzheimer's Disease Cohorts - Xi-Chen Zhu; Hui-Fu Wang; Teng Jiang; Huan Lu; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

The spatio-temporal characteristics of potential dengue risk assessed by Aedes aegypti and Aedes albopictus in high-epidemic areas - Chia-Hsien Lin; Tzai-Hung Wen; Hwa-Jen Teng; Niann-Tai Chang (Stochastic Environmental Research and Risk Assessment, 2016)

Nutraceuticals in Neurodegeneration and Aging - Wei-Yi Ong; Grace Y. Sun; W. Gibson Wood; Teng-Nan Lin (NeuroMolecular Medicine, 2016)

Clinacanthus nutans Extracts Modulate Epigenetic Link to Cytosolic Phospholipase A2 Expression in SH-SY5Y Cells and Primary Cortical Neurons - Charlene Siew-Hon Tan; Christabel Fung-Yih Ho; Swan-Ser Heng; Jui-Sheng Wu; Benny Kwong-Huat Tan; Yee-Kong Ng; Grace Y. Sun; Teng-Nan Lin; Wei-Yi Ong (NeuroMolecular Medicine, 2016)

Clinacanthus nutans Protects Cortical Neurons Against Hypoxia-Induced Toxicity by Downregulating HDAC1/6 - Hsin-Da Tsai; Jui-Sheng Wu; Mei-Han Kao; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Teng-Nan Lin (NeuroMolecular Medicine, 2016)

PPAR-γ Ameliorates Neuronal Apoptosis and Ischemic Brain Injury via Suppressing NF-κB-Driven p22phox Transcription - Jui-Sheng Wu; Hsin-Da Tsai; Wai-Mui Cheung; Chung Y. Hsu; Teng-Nan Lin (Molecular Neurobiology, 2016)

Microbial community in a multi-trophic aquaculture system of Apostichopus japonicus, Styela clava and microalgae - Jian Lin; Bao Ju; Yanan Yao; Xiaoming Lin; Ronglian Xing; Li Teng; Aili Jiang (Aquaculture International, 2016)

Inhibition of Autophagy by Estradiol Promotes Locomotor Recovery after Spinal Cord Injury in Rats - Chao-Wei Lin; Bi Chen; Ke-Lun Huang; Yu-Sen Dai; Hong-Lin Teng (Neuroscience Bulletin, 2016)

GSTM1 Null Genotype and GSTP1 Ile105Val Polymorphism Are Associated with Alzheimer’s Disease: a Meta-Analysis - Mo Wang; Yu Li; Lulu Lin; Guijun Song; Teng Deng (Molecular Neurobiology, 2016)

Hyperspectral analysis of soil organic matter in coal mining regions using wavelets, correlations, and partial least squares regression - Lixin Lin; Yunjia Wang; Jiyao Teng; Xuchen Wang (Environmental Monitoring and Assessment, 2016)

Typhoon Disturbance Mediates Elevational Patterns of Forest Structure, but not Species Diversity, in Humid Monsoon Asia - Chung-How Chi; Ryan W. McEwan; Chung-Te Chang; Chengyang Zheng; Zhijie Yang; Jyh-Min Chiang; Teng-Chiu Lin (Ecosystems, 2015)

Melatonin Ameliorates Arsenite-Induced Neurotoxicity: Involvement of Autophagy and Mitochondria - Y. C. Teng; Y. I. Tai; H. J. Huang; A. M. Y. Lin (Molecular Neurobiology, 2015)

Odontoblast β-catenin signaling regulates fenestration of mouse Hertwig’s epithelial root sheath - Ran Zhang; Yan Teng; Liang Zhu; JingTing Lin; Xiao Yang; Guan Yang; TieJun Li (Science China Life Sciences, 2015)

Associations between TRPV4 genotypes and body mass index in Taiwanese subjects - De-Min Duan; Semon Wu; Lung-An Hsu; Ming-Sheng Teng; Jeng-Feng Lin; Yu-Chen Sun; Ching-Feng Cheng; Yu-Lin Ko (Molecular Genetics and Genomics, 2015)

Observed features of temperature, salinity and current in central Chukchi Sea during the summer of 2012 - Yan He; Na Liu; Hongxia Chen; Fei Teng; Lina Lin; Huiwu Wang (Acta Oceanologica Sinica, 2015)

Novel Link of Anti-apoptotic ATF3 with Pro-apoptotic CTMP in the Ischemic Brain - Chien-Yu Huang; Jin-Jer Chen; Jui-Sheng Wu; Hsin-Da Tsai; Heng Lin; Yu-Ting Yan; Chung Y. Hsu; Yuan-Soon Ho; Teng-Nan Lin (Molecular Neurobiology, 2015)

GSK3β Promotes the Differentiation of Oligodendrocyte Precursor Cells via β-Catenin-Mediated Transcriptional Regulation - Liang Zhou; Chong-Yu Shao; Si-min Xu; Jiao Ma; Ya-Jun Xie; Lin Zhou; Peng Teng; Yin Wang; Mengsheng Qiu; Ying Shen (Molecular Neurobiology, 2014)

Clinical and microbiological characteristics of Klebsiella pneumoniae from community-acquired recurrent urinary tract infections - W. H. Lin; C. Y. Kao; D. C. Yang; C. C. Tseng; A. B. Wu; C. H. Teng; M. C. Wang; J. J. Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

15-Deoxy-∆12,14-PGJ2, by Activating Peroxisome Proliferator-Activated Receptor-Gamma, Suppresses p22phox Transcription to Protect Brain Endothelial Cells Against Hypoxia-Induced Apoptosis - Jui-Sheng Wu; Hsin-Da Tsai; Chien-Yu Huang; Jin-Jer Chen; Teng-Nan Lin (Molecular Neurobiology, 2014)

The rice OsDG2 encoding a glycine-rich protein is involved in the regulation of chloroplast development during early seedling stage - Quan Jiang; XiaoJing Ma; XiaoDi Gong; JianHui Zhang; Sheng Teng; JianLong Xu; DongZhi Lin; YanJun Dong (Plant Cell Reports, 2014)

Demography of the upward-shifting temperate woody species of the Rhododendron pseudochrysanthum complex and ecologically relevant adaptive divergence in its trailing edge populations - Chia-Ying Chen; Bo-Kai Liang; Jeng-Der Chung; Chung-Te Chang; Yi-Chiang Hsieh; Teng-Chiu Lin; Shih-Ying Hwang (Tree Genetics & Genomes, 2014)

Relating vegetation dynamics to temperature and precipitation at monthly and annual timescales in Taiwan using MODIS vegetation indices - Chung-Te Chang; Su-Fen Wang; Matthew A. Vadeboncoeur; Teng-Chiu Lin (International Journal of Remote Sensing, 2014)

Role of HO-1 in the Arsenite-Induced Neurotoxicity in Primary Cultured Cortical Neurons - Y. C. Teng; Y. I. Tai; Y. H. Lee; A. M. Y. Lin (Molecular Neurobiology, 2013)

Activating transcription factor 4 is involved in endoplasmic reticulum stress-mediated apoptosis contributing to vascular calcification - Xiao-Hui Duan; Jin-Rui Chang; Jing Zhang; Bao-Hong Zhang; Yu-Lin Li; Xu Teng; Yi Zhu; Jie Du; Chao-Shu Tang; Yong-Fen Qi (Apoptosis, 2013)

Moscatilin inhibits migration and metastasis of human breast cancer MDA-MB-231 cells through inhibition of Akt and Twist signaling pathway - Hui-Chen Pai; Li-Hsun Chang; Chieh-Yu Peng; Ya-Ling Chang; Chien-Chih Chen; Chien-Chang Shen; Che-Ming Teng; Shiow-Lin Pan (Journal of Molecular Medicine, 2013)

Role of K1 capsule antigen in cirrhotic patients with Escherichia coli spontaneous bacterial peritonitis in southern Taiwan - M. C. Wang; W. H. Lin; C. C. Tseng; A. B. Wu; C. H. Teng; J. J. Yan; J. J. Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Peroxisome Proliferator-Activated Receptor Gamma (PPAR-γ) and Neurodegenerative Disorders - Yu-Chang Chen; Jui-Sheng Wu; Hsin-Da Tsai; Chien-Yu Huang; Jin-Jer Chen; Grace Y. Sun; Teng-Nan Lin (Molecular Neurobiology, 2012)

Fasudil, a Rho-kinase inhibitor, protects against excessive endurance exercise training-induced cardiac hypertrophy, apoptosis and fibrosis in rats - Tsung-Jung Ho; Chi-Chang Huang; Chih-Yang Huang; Wan-Teng Lin (European Journal of Applied Physiology, 2012)

Oxidative stress in greater duckweed (Spirodela polyrhiza) caused by long-term NaCl exposure - In-Hwa Chang; Kai-Teng Cheng; Po-Chuan Huang; Yen-Yu Lin; Lee-Ju Cheng; Tai-Sheng Cheng (Acta Physiologiae Plantarum, 2012)

Blockade of acid-sensing ion channels protects articular chondrocytes from acid-induced apoptotic injury - Wei Hu; Fei-Hu Chen; Feng-Lai Yuan; Teng-Yue Zhang; Fan-Rong Wu; Chao Rong; Sheng Jiang; Jie Tang; Cheng-Cheng Zhang; Mei-Ying Lin (Inflammation Research, 2012)

Preferential involvement of mitochondria in Toll-like receptor 3 agonist-induced neuroblastoma cell apoptosis, but not in inhibition of cell growth - Jiin-Haur Chuang; Tsu-Kung Lin; Ming-Hong Tai; Chia-Wei Liou; Sheng-Teng Huang; Chia-Ling Wu; Hung-Yi Lin; Pei-Wen Wang (Apoptosis, 2012)

Matrix metalloproteinase-9 as new biomarkers of severity in multiple organ dysfunction syndrome caused by trauma and infection - Lin Teng; Min Yu; Jun-ming Li; Hua Tang; Jing Yu; Li-hua Mo; Jing Jin; Xian-zhe Liu (Molecular and Cellular Biochemistry, 2012)

Mechanism of Monoclonal Antibody-Coupled Staphylococcus Superantigen-A Induced Apoptosis in Human Bladder Cancer Cells - Conghui Han; Zhen Gong; Lin Hao; Jianjun Yang; Jianpeng Hu; Bingzheng Dong; Tao Fan; Wenhao Tang; Gaojun Teng (Cell Biochemistry and Biophysics, 2011)

Assessing growing season beginning and end dates and their relation to climate in Taiwan using satellite data - Chung-Te Chang; Teng-Chiu Lin; Su-Fen Wang; Matthew A. Vadeboncoeur (International Journal of Remote Sensing, 2011)

An easy and efficient protocol in the production of pflp transgenic banana against Fusarium wilt - Mei-Kuen Yip; Sin-Wan Lee; Kuei-Ching Su; Yi-Hsien Lin; Tai-Yang Chen; Teng-Yung Feng (Plant Biotechnology Reports, 2011)

The Biodegradation of Zein In Vitro and In Vivo and its Application in Implants - Teng Lin; Chuanhua Lu; Ligen Zhu; Tao Lu (AAPS PharmSciTech, 2011)

Typhoon Disturbance and Forest Dynamics: Lessons from a Northwest Pacific Subtropical Forest - Teng-Chiu Lin; Steven P. Hamburg; Kuo-Chuan Lin; Lih-Jih Wang; Chung-Te Chang; Yue-Joe Hsia; Matthew A. Vadeboncoeur; Cathy M. Mabry McMullen; Chiung-Pin Liu (Ecosystems, 2011)

Morphological changes of Fusarium oxysporum induced by CF66I, an antifungal compound from Burkholderia cepacia - Xin Li; Hui-Ying Yu; Yi-Feng Lin; Hong-Mei Teng; Lei Du; Guo-Gang Ma (Biotechnology Letters, 2010)

Interspecific hybrids between Chrysanthemum grandiflorum (Ramat.) Kitamura and C. indicum (L.) Des Moul. and their drought tolerance evaluation - Chun-Qing Sun; Fa-Di Chen; Nian-Jun Teng; Zhao-Lei Liu; Wei-Min Fang; Xi-Lin Hou (Euphytica, 2010)

Anti-apoptotic Actions of PPAR-γ Against Ischemic Stroke - Wen-Hsuan Fong; Hsin-Da Tsai; Yu-Chang Chen; Jui-Sheng Wu; Teng-Nan Lin (Molecular Neurobiology, 2010)

Involvement of the residues of GSKIP, AxinGID, and FRATtide in their binding with GSK3β to unravel a novel C-terminal scaffold-binding region - Shen-Long Howng; Chi-Ching Hwang; Chia-Yi Hsu; Meng-Yu Hsu; Chun-Yen Teng; Chia-Hua Chou; Mei-Feng Lee; Chia-Hung Wu; Shean-Jaw Chiou; Ann-Shung Lieu; Joon-Khim Loh; Chia-Ning Yang; et al. (Molecular and Cellular Biochemistry, 2010)

Sun/shade adaptations of the photosynthetic apparatus of Hoya carnosa, an epiphytic CAM vine, in a subtropical rain forest in northeastern Taiwan - Craig E. Martin; Rebecca C.-C. Hsu; Teng-Chiu Lin (Acta Physiologiae Plantarum, 2010)

In vitro activities of doripenem and other carbapenems against clinically important bacteria isolated in intensive care units: nationwide data from the SMART Programme - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

The speed of mitochondrial movement is regulated by the cytoskeleton and myosin in Picea wilsonii pollen tubes - Maozhong Zheng; Qinli Wang; Yan Teng; Xiaohua Wang; Feng Wang; Tong Chen; Jozef Šamaj; Jinxing Lin; David C. Logan (Planta, 2010)

Monoamine oxidase A gene polymorphisms and enzyme activity associated with risk of gout in Taiwan aborigines - Hung-Pin Tu; Albert Min-Shan Ko; Shu-Jung Wang; Chien-Hung Lee; Rod A. Lea; Shang-Lun Chiang; Hung-Che Chiang; Tsu-Nai Wang; Meng-Chuan Huang; Tsan-Teng Ou; Gau-Tyan Lin; Ying-Chin Ko (Human Genetics, 2010)

Metabolomics investigation of exercise-modulated changes in metabolism in rat liver after exhaustive and endurance exercises - Chi-Chang Huang; Wan-Teng Lin; Feng-Lin Hsu; Pi-Wen Tsai; Chia-Chung Hou (European Journal of Applied Physiology, 2010)

Factors affecting seed set in the crosses between Dendranthema grandiflorum (Ramat.) Kitamura and its wild species - Chun-Qing Sun; Fa-Di Chen; Nian-Jun Teng; Zhao-Lei Liu; Wei-Min Fang; Xi-Lin Hou (Euphytica, 2010)

Endurance training accelerates exhaustive exercise-induced mitochondrial DNA deletion and apoptosis of left ventricle myocardium in rats - Chi-Chang Huang; Tien-Jen Lin; Chun-Chieh Chen; Wan-Teng Lin (European Journal of Applied Physiology, 2009)

Study on Tracheal Collapsibility, Compliance, and Stress by Considering Nonlinear Mechanical Property of Cartilage - Zhongzhao Teng; Ignacio Ochoa; Zhiyong Li; Zijie Liao; Yihan Lin; Manuel Doblare (Annals of Biomedical Engineering, 2009)

Nationwide surveillance of antimicrobial resistance among Haemophilus influenzae and Streptococcus pneumoniae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Effect of CO2 enrichment on the glucosinolate contents under different nitrogen levels in bolting stem of Chinese kale (Brassica alboglabra L.) - Gui-xiao La; Ping Fang; Yi-bo Teng; Ya-juan Li; Xian-yong Lin (Journal of Zhejiang University-SCIENCE B, 2009)

Nationwide surveillance of antimicrobial resistance among Enterobacteriaceae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Baicalein attenuates intimal hyperplasia after rat carotid balloon injury through arresting cell-cycle progression and inhibiting ERK, Akt, and NF-κB activity in vascular smooth-muscle cells - Chieh-Yu Peng; Shiow-Lin Pan; Ying-Wen Huang; Jih-Hwa Guh; Ya-Ling Chang; Che-Ming Teng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Denbinobin induces apoptosis by apoptosis-inducing factor releasing and DNA damage in human colorectal cancer HCT-116 cells - Tzu-Hsuan Chen; Shiow-Lin Pan; Jih-Hwa Guh; Chien-Chih Chen; Yao-Ting Huang; Hui-Chen Pai; Che-Ming Teng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Production of soft rot resistant calla lily by expressing a ferredoxin-like protein gene (pflp) in transgenic plants - Mei-Kuen Yip; Hsiang-En Huang; Mang-Jye Ger; Shih-Hua Chiu; Yuh-Chih Tsai; Chin-I Lin; Teng-Yung Feng (Plant Cell Reports, 2007)

Functional polymorphisms of FGA, encoding α fibrinogen, are associated with susceptibility to venous thromboembolism in a Taiwanese population - Yu-Lin Ko; Lung-An Hsu; Tsu-Shiu Hsu; Chia-Ti Tsai; Ming-Sheng Teng; Semon Wu; Chi-Jen Chang; Ying-Shiung Lee (Human Genetics, 2006)

Characterizinig Precipitation Chemistry in Changhua, Central Taiwan Using Weather Conditions And Multivariate Analysis - Chuan-Te Chang; Teng-Chiu Lin; Mei-Li Hsueh (Water, Air, & Soil Pollution, 2005)

Clinical and electrophysiological characterization of a novel mutation R863X in HERG C-terminus associated with long QT syndrome - Siyong Teng; Lijuan Ma; Yingxue Dong; Chunxia Lin; Jue Ye; Robert Bhring; Vitya Vardanyan; Yanzong Yang; Zhihu Lin; Olaf Pongs; Rutai Hui (Journal of Molecular Medicine, 2004)

Ferredoxin from sweet pepper (Capsicum annuum L.) intensifying harpinpss-mediated hypersensitive response shows an enhanced production of active oxygen species (AOS) - Badri Venkata Dayakar; Hao-Jan Lin; Cheng-Hsien Chen; Mang-Jye Ger; Bor- Heng Lee; Chia-Hwei Pai; David Chow; Hsiang-En Huang; Shaw-Yhi Hwang; Mei-Chu Chung; Teng-Yung Feng (Plant Molecular Biology, 2003)

Transdermal Delivery of Antisense Oligonucleotides with Microprojection Patch (macroflux®) Technology - WeiQi Lin; Michel Cormier; Ahmad Samiee; Angie Griffin; Bonny Johnson; Ching-Leou Teng; Gregory E. Hardee; Peter E. Daddona (Pharmaceutical Research, 2001)

cDNA cloning and characterization of a plant protein that may be associated with the harpinPSS-mediated hypersensitive response - Cheng-hsien Chen; Hao-jan Lin; Mang-jye Ger; David Chow; Teng-yung Feng (Plant Molecular Biology, 2000)